Inorganic microparticle dispersion liquid
By using an inorganic fine particles dispersion liquid containing inorganic fine particles, liquid dispersion medium and alkoxysilane on the surface of the solar cell protective glass, a layer of inorganic fine particles with higher light transmittance and excellent antifouling properties, the transparentness in the prior art is solved Problems of insufficient light rate and stain resistance.
Patent Information
- Application Number
- CN202380048549.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2023-09-27
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to form a layer with higher light transmittance and excellent stain resistance on the protective glass surface of a solar cell.
Using an inorganic fine particle dispersion liquid, the liquid comprises inorganic fine particles, a liquid dispersion medium A with a boiling point greater than 121°C and less than 190°C, a liquid dispersion medium B with a boiling point less than 100°C, water, alkoxysilane and a pore-forming agent, through The coating and dispersion medium removal process forms an inorganic fine particle layer, and a pore structure is imparted by heat treatment.
It realizes an inorganic particle layer with higher light transmittance and excellent stain resistance, and improves the optical performance and stain resistance of solar cell protective glass.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to an inorganic particle dispersion. Background Art
[0002] In the past, in order to prevent the flash of display, etc., an anti-reflection film was formed on the display surface. For example, in patent document 1, as the material of anti-reflection film, an inorganic particle dispersion liquid comprising an inorganic particle chain, inorganic particles and a liquid dispersion medium is recorded. In addition, in patent document 2, a coating composition for forming a hard coat layer for a plastic substrate is recorded, which comprises an organosilicon compound, silicon dioxide particles, a curing agent, a leveling agent and a solvent comprising water and an organic solvent. And, in patent document 3, as a coating liquid for a laminate having a good transmittance that can be provided by forming a film on a substrate, etc., a coating liquid containing a hydrolysis condensate of a silane compound with an alkoxy group, a curing catalyst, and a dispersion medium is recorded.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2006-327187
[0006] Patent Document 2: WO2019 / 044838
[0007] Patent Document 3: WO2020 / 241745 Summary of the invention
[0008] Problems to be solved by the invention
[0009] In recent years, an anti-reflection film is formed on the surface of the protective glass of a solar cell in order to improve power generation efficiency. However, the light transmittance of the protective glass of the solar cell is required to be further improved.
[0010] An object of the present invention is to provide an inorganic fine particle dispersion capable of forming a layer having higher light transmittance and excellent antifouling properties.
[0011] Means used to solve problems
[0012] The present inventors have conducted intensive studies in view of such background and have completed the present invention as a result.
[0013] That is, the present invention relates to the following contents, but is not limited thereto.
[0014] [1] An inorganic particle dispersion, comprising: inorganic particles, a liquid dispersion medium A having a boiling point greater than 121° C. and less than 190° C., a liquid dispersion medium B having a boiling point less than 100° C., water, an alkoxysilane, and a pore former, wherein the content of the liquid dispersion medium A is greater than or equal to 0.5% by mass and less than 15.0% by mass when the total amount of the inorganic particle dispersion is 100% by mass. [2] to [9] are preferred modes or embodiments of the present invention, respectively.
[0015] [2] The inorganic particle dispersion as described in [1], wherein the ratio of the weight of SiO2 contained in the alkoxysilane to the weight of the inorganic particles ([the weight of SiO2 contained in the alkoxysilane] / [the weight of the inorganic particles]) is greater than 0.10.
[0016] [3] The inorganic fine particle dispersion according to [1] or [2], wherein the alkoxysilane has a structure represented by the following general formula (1).
[0017] General formula (1)
[0018]
[0019] (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms. n is an integer of 2 to 1000.)
[0020] [4] The inorganic fine particle dispersion according to any one of [1] to [3], wherein the inorganic fine particles are inorganic fine particles containing silica particles.
[0021] [5] The inorganic fine particle dispersion according to [1], wherein the pore former is an organic ammonium salt.
[0022] [6] An inorganic fine particle dispersion as described in any one of [1] to [5], wherein the ratio of the weight of the pore-forming agent to the total weight of SiO2 contained in the alkoxysilane ([weight of the pore-forming agent] / [total weight of SiO2 contained in the alkoxysilane]) is greater than 0.10.
[0023] [7] A method for producing a laminate, wherein the method for producing a laminate comprises: a step of coating the inorganic particle dispersion described in any one of [1] to [6] on a substrate (coating step); and a step of removing liquid dispersion medium A, liquid dispersion medium B and water from the inorganic particle dispersion coated on the substrate to form an inorganic particle layer on the substrate (dispersion medium removal step).
[0024] [8] The method for producing a laminated body according to [7], further comprising a heat treatment step after the dispersion medium removal step.
[0025] [9] A laminated body, wherein the laminated body can be obtained by the method described in [7] or [8].
[0026] Effects of the Invention
[0027] According to the present invention, it is possible to provide an inorganic fine particle dispersion liquid capable of forming a layer having higher light transmittance and excellent antifouling properties.
[0028] According to the present invention, it is also possible to provide a laminate having a layer having a higher light transmittance and excellent antifouling properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] exist Figure 1 A scanning electron microscope photograph of the cross section of Example 18 is shown in FIG.
[0030] exist Figure 2 A scanning electron microscope photograph of a cross section of Comparative Example 10 is shown in FIG.
[0031] exist Figure 3 A scanning electron microscope photograph of the cross section of Comparative Example 12 is shown in FIG. DETAILED DESCRIPTION
[0032] Hereinafter, one embodiment of the present invention will be described in detail.
[0033] <Inorganic fine particle dispersion>
[0034] The inorganic particle dispersion of the present invention is an inorganic particle dispersion comprising inorganic particles, a liquid dispersion medium A having a boiling point greater than 121° C. and less than 190° C., a liquid dispersion medium B having a boiling point less than 100° C., water, an alkoxysilane, and a pore-forming agent, wherein, when the total amount of the inorganic particle dispersion is set to 100% by mass, the content of the liquid dispersion medium A is greater than or equal to 0.5% by mass and less than 15.0% by mass.
[0035] [Inorganic particles]
[0036] In the present invention, the inorganic particles may be inorganic particles X having a primary particle size of 1 nm or more and 60 nm or less, or inorganic particles Y formed by connecting a plurality of inorganic particles having a primary particle size of 1 nm or more and 60 nm or less. Here, the expression "plural connected" includes not only a state connected in a straight line (chain), but also a state connected in a bent manner, a state connected in a ring shape, and a branched state.
[0037] The primary particle size of the inorganic fine particles is evaluated as the number average of particle sizes of 50 or more particles observed with a transmission microscope. The state of "a plurality of inorganic fine particles connected" in the inorganic fine particles Y can also be determined by observation with a transmission microscope.
[0038] As the material of the inorganic particles, for example, silicon oxide (silicon dioxide), titanium oxide, aluminum oxide, zinc oxide, tin oxide, calcium carbonate, barium sulfate, talc, kaolin, etc., one or more of which can be used. From the viewpoint of dispersibility in the inorganic particle dispersion, silicon dioxide is preferred, and colloidal silicon dioxide and fumed silicon dioxide are further preferred among silicon dioxides, and colloidal silicon dioxide is particularly preferred. Colloidal silicon dioxide can be colloidal silicon dioxide containing colloidal silicon dioxide particles at a solid content concentration of 5% to 50% by weight, for example, 5% to 40% by weight, preferably 10% to 30% by weight. The above-mentioned inorganic particles can use a liquid obtained by dispersing in various solvents as a raw material liquid. Examples of the solvent include: alcohol solvents such as methanol, ethanol, isopropanol, ethylene glycol, and ethylene glycol mono-n-propyl ether; amide solvents such as dimethylacetamide and N-methylpyrrolidone; aromatic solvents such as toluene; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as ethyl acetate; water, etc., and a plurality of these solvents can also be mixed and used.
[0039] Preferred are alcohol solvents such as methanol, ethanol, isopropanol, ethylene glycol, ethylene glycol mono-n-propyl ether and water, more preferred are methanol, ethanol, isopropanol and water, more preferred are ethanol, isopropanol and water, and more preferred is water.
[0040] The primary particle size of the inorganic fine particles is 1 nm to 100 nm, more preferably 1 nm to 60 nm, more preferably 1 nm to 50 nm, more preferably 1 nm to 30 nm, more preferably 1 nm or more and less than 30 nm, more preferably 1 nm to 25 nm.
[0041] The inorganic particles may be inorganic fine particles X having a primary particle diameter of 1 nm to 60 nm, or inorganic fine particles Y formed by connecting a plurality of inorganic fine particles having a primary particle diameter of 1 nm to 60 nm.
[0042] From the viewpoint of taking into account both transmittance and coating strength, the primary particle size of the inorganic fine particles X is preferably 1 nm or more and 50 nm or less, more preferably 1 nm or more and 30 nm or less, more preferably 1 nm or more and less than 30 nm, more preferably 1 nm or more and 25 nm or less, more preferably 1 nm or more and 20 nm or less, more preferably 3 nm or more and 15 nm or less, and particularly preferably 3 nm or more and 10 nm or less.
[0043] From the viewpoint of having both transmittance and coating strength, the primary particle size of the inorganic microparticle Y formed by connecting multiple inorganic microparticles with a primary particle size of 1 nm or more and 60 nm or less is preferably 1 nm or more and 50 nm or less, more preferably 1 nm or more and 45 nm or less, more preferably 1 nm or more and 30 nm or less, more preferably 1 nm or more and 30 nm or less, more preferably 1 nm or more and 25 nm or less, more preferably 5 nm or more and 20 nm or less, and particularly preferably 5 nm or more and 15 nm or less.
[0044] The average particle diameter of inorganic particles Y is preferably 1nm to 500nm, more preferably 1nm to 400nm, which can be obtained by dynamic light scattering or Sears method. The determination of the average particle diameter using dynamic light scattering can be carried out using a commercially available particle size distribution measuring device. Sears method refers to the method described in Analytical Chemistry, Vol. 28, pp. 1981-1983, 1956, which is an analytical method suitable for measuring the average particle diameter of silica particles, and is a method for calculating the surface area and the equivalent spherical diameter by the amount of NaOH consumed by making the colloidal silica dispersion liquid of pH=3 reach pH=9. The equivalent spherical diameter thus obtained is used as the average particle diameter.
[0045] In addition, only inorganic particles X can be used, only inorganic particles Y can be used, and inorganic particles X and inorganic particles Y can also be used in combination. The mixing ratio of inorganic particles X and inorganic particles Y is not particularly limited. As a mode, from the viewpoint of transmittance and coating strength, it is preferred to use the two, (the mass of inorganic particles Y) / [(the mass of inorganic particles X)+(the mass of inorganic particles Y)] The value is preferably more than 0.01 and less than 0.99, more preferably more than 0.10 and less than 0.95, more preferably more than 0.20 and less than 0.95, more preferably more than 0.40 and less than 0.95, more preferably more than 0.50 and less than 0.90, more preferably more than 0.60 and less than 0.80, more preferably more than 0.71 and less than 0.80. In addition, as inorganic particles X, one or more inorganic particles can be used, and as inorganic particles Y, one or more inorganic particles can be used.
[0046] The containing rate of inorganic particles is not particularly limited, from the viewpoint of the transparency of the obtained coating and the dispersibility in the inorganic particle dispersion liquid, when the gross weight of the inorganic particle dispersion liquid is set to 100 weight %, the containing rate of inorganic particles is preferably more than 0.1 mass % and less than 10 weight %, more preferably more than 0.1 mass % and less than 7.5 weight %, further preferably more than 0.2 mass % and less than 5.0 weight %, particularly preferably more than 1 mass % and less than 5.0 weight %. Below, sometimes the containing rate of inorganic particles in the case where the inorganic particle dispersion liquid is set to 100 mass % as a whole is recorded as "the solid component concentration of inorganic particles in the inorganic particle dispersion liquid". In addition, " containing rate of inorganic particles " refers to the total value of the containing rate of inorganic particles X and the containing rate of inorganic particles Y.
[0047] From the viewpoint of dispersibility, coating and film formation in the dispersion, the inorganic particles in the inorganic particle dispersion can be surface treated. As the method for surface treatment, known methods can be used, and suitable additives can be cited for processing. The surface treatment of inorganic particles can be carried out by mixing the liquid comprising inorganic particles, additives and solvents.
[0048] Specific examples of the inorganic fine particles X include: commercially available Snowtex (registered trademark) ST-XS, ST-OXS, ST-NXS, ST-CXS, ST-S, ST-OS, ST-NS, ST-3O, ST-O, ST-N, ST-C, ST-AK, ST-5O-T, ST-O-4O, ST-N-4O, ST-CM, ST-3OL, ST-OL, ST-AK-L, ST-YL, ST-OYL, ST-AK-YL in the form of a methanol dispersion; commercially available methanol silica sol (registered trademark), MA-ST-M, MA-ST-L in the form of an isopropyl alcohol dispersion; commercially available IPA-ST, IPA-ST-L in the form of an ethylene glycol monopropyl ether dispersion. NPC-ST-30, a commercial product, in the form of a toluene dispersion; TOL-ST, a commercial product, in the form of a toluene dispersion; MEK-ST-40, MEK-ST-L, MEK-EC-2130Y, MEK-EC-2430Z, MEK-AC-2140Z, MEK-AC-4130Y, and MEK-AC-5140Z, which are commercial products, in the form of a 2-butanone dispersion; MIBK-ST, MIBK-ST-L, MIBK-AC-2140Z, and MIBK-SD-L, which are commercial products in the form of a 4-methyl-2-pentanone dispersion; CHO-ST-M, which is in the form of a cyclohexanone dispersion; EAC-ST, a commercial product, in the form of an ethyl acetate dispersion; and PMA-ST, which is in the form of a propylene glycol 1-monomethyl ether 2-acetate dispersion. Among them, inorganic fine particles in the form of aqueous dispersion are preferred, with ST-OXS, ST-NXS, ST-CXS, ST-OS, ST-NS, ST-O, ST-N, ST-C, ST-O-4O, ST-N-4O, ST-CM, ST-OL and ST-OYL being particularly preferred, and ST-OXS, ST-OS, ST-O, ST-O-4O, ST-OL and ST-OYL being more preferred.
[0049] Specifically, inorganic fine particles Y include, for example, commercially available Snowtex (registered trademark) ST-UP, ST-OUP, ST-PS-S, ST-PS-SO, ST-PS-M, and ST-PS-MO in the form of aqueous dispersions; commercially available MA-ST-UP in the form of methanol dispersions; commercially available IPA-ST-UP in the form of isopropyl alcohol dispersions; and commercially available MEK-ST-UP in the form of 2-butanone dispersions. Among them, inorganic fine particles in the form of aqueous dispersions are preferred, with ST-OUP, ST-PS-SO, and ST-PS-MO being particularly preferred, and ST-OUP being more preferred.
[0050] The method for synthesizing the inorganic fine particles X and Y is not particularly limited, and examples thereof include hydrolysis and / or condensation of metal alkoxides, thermal decomposition of metal salts, pulverization and / or crushing of metal oxides, precipitation of metal salt aqueous solutions, and hydrothermal treatment of metal salt aqueous solutions.
[0051] From the viewpoint of dispersibility, silicon dioxide is preferably synthesized by the following methods: a method in which an aqueous sodium silicate solution is subjected to ion exchange using an ion exchange resin or the like, followed by particle growth and concentration (sometimes also referred to as a water glass method); a method in which an aqueous sulfuric acid solution is added to an aqueous sodium silicate solution and neutralized, followed by particle growth and concentration (sometimes also referred to as a sedimentation method); a method in which silicon tetrachloride is thermally decomposed; a method in which an alkoxysilane is hydrolyzed and condensed (sometimes referred to as a sol-gel method), and the like.
[0052] In the case of the method of synthesizing by ion exchange of sodium silicate, from the viewpoint of forming an inorganic fine particle layer with high light transmittance, the sodium ion content in the silica sol is preferably 0.5% by weight or less, more preferably 0.05% by weight or less, and further preferably 0.03% by weight or less, in terms of the amount of Na2O.
[0053] [Liquid dispersion medium A]
[0054] In the present invention, liquid dispersion medium A is a liquid having a boiling point of greater than 121° C. and less than 190° C. at atmospheric pressure (1013.25 hPa). When the entire inorganic fine particle dispersion is 100 mass %, the content of liquid dispersion medium A is greater than or equal to 0.5 mass % and less than 15 mass %.
[0055] The boiling point range of the liquid dispersion medium A is preferably 125°C or higher and lower than 190°C, more preferably 135°C or higher and lower than 190°C, more preferably 150°C or higher and lower than 190°C, more preferably 155°C or higher and lower than 190°C, more preferably 155°C or higher and lower than 180°C, more preferably 160°C or higher and lower than 180°C, and more preferably 170°C or higher and lower than 180°C.
[0056] As the lower limit of the content of the liquid dispersion medium A, from the perspective of suppressing the agglomeration of inorganic particles when the coating film is dried by using the liquid dispersion medium A, and improving the transmittance and coating film strength, when the entire inorganic particle dispersion is set to 100 mass %, it is preferred that the liquid dispersion medium A is contained in an amount of 0.7 mass % or more, preferably 1.0 mass % or more, preferably 1.2 mass % or more, and further preferably 1.4 mass % or more. In addition, as the upper limit of the content of the liquid dispersion medium A, from the aspect of deterioration of storage stability due to gelation of the inorganic fine particle dispersion when an excessive amount of liquid dispersion medium A is contained, when the entire inorganic fine particle dispersion is set to 100 mass %, it is preferred that the liquid dispersion medium A is contained in an amount of 13.0 mass % or less, more preferably 12.0 mass % or less, more preferably 10.0 mass % or less, more preferably 8.0 mass % or less, more preferably 6.0 mass % or less, and more preferably 3.0 mass % or less.
[0057] As the liquid dispersion medium A, δtA defined by the following formula can be exemplified as 20 MPa. 0.5 Above and 40Mpa 0.5 The following liquid dispersion media are exemplified as good examples.
[0058]
[0059] (In formula (1), δDA, δPA, and δHA represent the dispersion terms in the Hansen solubility parameters of the liquid dispersion medium A (MPa) 0.5 ), polarity term (Mpa 0.5 ), hydrogen bonding term (Mpa 0.5 ). )
[0060] The above-mentioned δDA, δPA, and δHA are calculated using "HSPiP 5th 5.2.06" which is a generally available commercial software and applying a method called Y-MB in the software.
[0061] As the preferred range of δtA, the upper limit is preferably 39 MPa 0.5 Below, more preferably 35.5Mpa 0.5 Below, more preferably 34Mpa 0.5 The lower limit is preferably 25Mpa 0.5 More than 29Mpa 0.5 Above, more preferably 30Mpa 0.5The liquid dispersion medium A having δtA within such a range can obtain high affinity with silica particles, and thus has good coating properties.
[0062] From the viewpoint of coating properties, the lower limit of the molecular weight of the liquid dispersion medium A is preferably 60 or more, more preferably 70 or more, further preferably 90 or more, and particularly preferably 100 or more. The upper limit is preferably 300 or less, more preferably 200 or less, further preferably 170 or less, and particularly preferably 140 or less.
[0063] Examples of the type of the liquid dispersion medium A include, but are not limited to, ethers, esters, alcohols, ketones, amines, amides, and sulfoxides. Specific examples of the liquid dispersion medium A include, but are not limited to, 2-methoxyethyl acetate, isoamyl acetate, propylene glycol 1-monomethyl ether 2-acetate, 1-propoxy-2-propanol, N,N-dimethylformamide, 2-ethoxyethyl acetate, dimethyl sulfoxide, dipropylene glycol dimethyl ether, n-amyl acetate, ethyl acetoacetate, acetylacetone (2,4-pentanedione), 1-hexanol, furfuryl alcohol, 1-pentanol, dibutyl ether, 2-butoxyethanol (ethylene glycol monobutyl ether), 2-methoxyethanol (ethylene glycol monomethyl ether), 2-ethoxyethanol (ethylene glycol monoethyl ether), 2-ethyl Hexanol, N,N-dimethylacetamide, ethyl lactate, diethylene glycol ethyl methyl ether, 3-methoxybutyl acetate, 1,2-propylene glycol, 3-methoxy-3-methylbutanol, propylene glycol 1-monobutyl ether, 1-ethoxy-2-propanol, 3-methoxy-1-propanol, 3-methoxy-1-butanol, ethylene glycol mono-tert-butyl ether, 2-isopropoxyethanol, 2-propoxyethanol, 2-isobutoxyethanol, 2-allyloxyethanol, tetrahydrofurfuryl alcohol, 2-hydroxyethyl acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, 1,2-diacetoxypropane, 3-methoxy-3-methylbutyl acetate.
[0064] Preferred liquid dispersion medium A includes any one of an alcohol liquid dispersion medium, a liquid dispersion medium having an ether bond, and a liquid dispersion medium having an ester bond. More preferably, a liquid dispersion medium including any one of an alcohol liquid dispersion medium, a liquid dispersion medium having an ether bond, and a liquid dispersion medium having an ester bond and not containing a nitrogen atom can be included. When such a liquid dispersion medium A is used, coating properties become better.
[0065] As one embodiment of the inorganic fine particle dispersion, the liquid dispersion medium A is preferably alcohol. When the liquid dispersion medium A is alcohol, the compatibility of the inorganic fine particle component during coating with the alkoxysilane described below is improved, coating properties are improved, and a laminate having high coating strength (high adhesion of the coating to the substrate) can be obtained.
[0066] When the liquid dispersion medium A is an alcohol, monohydric alcohol can be cited as a good example. In addition, it is preferred to have an alcohol of any one or more of an ether bond and an ester bond. When the liquid dispersion medium A is such an alcohol, the dispersion and coating properties of the inorganic particles become good. As such a specific example, it is possible to enumerate: 1-propoxy-2-propanol, 1-hexanol, furfuryl alcohol, 1-pentanol, 2-butoxyethanol (ethylene glycol monobutyl ether), 2-methoxyethanol (ethylene glycol monomethyl ether), 2-ethoxyethanol (ethylene glycol monoethyl ether), 2-ethylhexanol, ethyl lactate, 3-methoxy-3-methylbutanol, propylene glycol 1-monobutyl ether, 1-ethoxy-2-propanol, 3-methoxy-1-propanol, 3-methoxy-1-butanol, ethylene glycol monotert-butyl ether, 2-isopropoxyethanol, 2-propoxyethanol, 2-isobutoxyethanol, 2-allyloxyethanol, tetrahydrofurfuryl alcohol, 2-hydroxyethyl acetate.
[0067] As liquid dispersion medium A, in the alcohol that is a monohydric alcohol and has any one or more of ether bond and ester bond, from the viewpoint of dispersion and coating property of inorganic particles, it is more preferred to list the alcohol that can be a monohydric alcohol and has ether bond. As such specific example, it is possible to list: 1-propoxy-2-propanol, furfuryl alcohol, 2-butoxyethanol (ethylene glycol monobutyl ether), 2-methoxyethanol (ethylene glycol monomethyl ether), 2-ethoxyethanol (ethylene glycol monoethyl ether), 2-ethylhexyl alcohol, 3-methoxy-3-methylbutanol, propylene glycol 1-monobutyl ether, 1-ethoxy-2-propanol, 3-methoxy-1-propanol, 3-methoxy-1-butanol, ethylene glycol monotert-butyl ether, 2-isopropoxyethanol, 2-propoxyethanol, 2-isobutoxyethanol, 2-allyloxyethanol, tetrahydrofurfuryl alcohol. More preferably, 1-propoxy-2-propanol, 2-butoxyethanol (ethylene glycol monobutyl ether), 2-ethylhexanol, 3-methoxy-3-methylbutanol, propylene glycol 1-monobutyl ether, 3-methoxy-1-propanol, 3-methoxy-1-butanol, ethylene glycol mono-tert-butyl ether, 2-isopropoxyethanol, 2-propoxyethanol, 2-isobutoxyethanol, 2-allyloxyethanol, and tetrahydrofurfuryl alcohol are mentioned. More preferably, 2-butoxyethanol (ethylene glycol monobutyl ether), 2-ethylhexanol, 3-methoxy-3-methylbutanol, propylene glycol 1-monobutyl ether, 3-methoxy-1-propanol, 3-methoxy-1-butanol, ethylene glycol mono-tert-butyl ether, 2-propoxyethanol, 2-isobutoxyethanol, and tetrahydrofurfuryl alcohol are mentioned. More preferably, 3-methoxy-3-methylbutanol and 3-methoxy-1-butanol are mentioned. Still more preferably, it is 3-methoxy-3-methylbutanol.
[0068] [Liquid dispersion medium B]
[0069] In the present invention, the liquid dispersion medium B is a liquid having a boiling point of less than 100° C. at atmospheric pressure (1013.25 hPa).
[0070] As the liquid dispersion medium B, δtB defined by the following formula can be exemplified as 15 MPa. 0.5 Above and 39Mpa 0.5 The following liquid dispersion media are exemplified as good examples.
[0071]
[0072] (In the formula, δDB, δPB, and δHB represent the dispersion terms in the Hansen solubility parameters of the liquid dispersion medium B (MPa 0.5 ), polarity term (Mpa 0.5 ), hydrogen bonding term (Mpa 0.5 ). )
[0073] The above-mentioned δDB, δPB, and δHB are calculated by using "HSPiP 5th 5.2.06" which is a generally available commercial software and applying a method called Y-MB in the software.
[0074] As the preferred range of δtB, the upper limit is preferably 32 MPa 0.5 Below, preferably 31Mpa 0.5 Below, more preferably 27Mpa 0.5 The lower limit is preferably 18Mpa 0.5 More than 23Mpa 0.5 More preferably 25Mpa 0.5 The liquid dispersion medium B having δtB within such a range can obtain high affinity with silica particles and improve coating properties.
[0075] As the type of liquid dispersion medium B, for example, ethers, esters, alcohols, etc. can be listed, as ethers, for example, diethyl ether can be listed, as esters, for example, methyl acetate and ethyl acetate can be listed, as alcohols, for example, methanol, ethanol, tert-butyl alcohol, sec-butyl alcohol, isopropyl alcohol and n-propyl alcohol can be listed. From the viewpoint of dispersibility of inorganic particles in the inorganic particle dispersion, alcohols are preferred, methanol, ethanol and isopropyl alcohol are more preferred, ethanol and isopropyl alcohol are particularly preferred, and from the viewpoint of safety, ethanol is more preferred.
[0076] The content of the liquid dispersion medium B is not particularly limited, but from the viewpoint of coating properties and storage stability, when the entire inorganic fine particle dispersion is 100.0 mass %, the lower limit is preferably 20.0 mass % or more, more preferably 30.0 mass % or more, more preferably 40.0 mass % or more, more preferably 50.0 mass % or more, and more preferably 60.0 mass % or more of the liquid dispersion medium B. The upper limit of the content of the liquid dispersion medium B is preferably 95.0 mass % or less, more preferably 90.0 mass % or less, more preferably 85.0 mass % or less, and more preferably 80.0 mass % or less of the liquid dispersion medium B.
[0077] [water]
[0078] The inorganic particle dispersion of the present invention includes water. As the lower limit of the content of water, from the viewpoint of coating property and storage stability, when the inorganic particle dispersion is set to 100.0 mass % as a whole, preferably include more than 1.0 mass %, more preferably include more than 3.0 mass %, more preferably include more than 5.0 mass %, more preferably include more than 8.0 mass %, more preferably include more than 10.0 mass %. In addition, as the upper limit of the content of water, from the viewpoint of coating property, preferably include less than 55.0 mass %, more preferably include less than 50.0 mass %, more preferably include less than 45.0 mass %, more preferably include less than 35.0 mass %, more preferably include less than 25.0 mass %, more preferably include less than 20.0 mass % water.
[0079] [Alkoxysilane]
[0080] The inorganic particle dispersion of the present invention comprises alkoxysilane, and the alkoxysilane can be a condensate of alkoxysilane. In the alkoxysilane, the alkoxy group can be partially hydrolyzed, and can also be further condensed in the hydrolyzed part. In this specification, "hydrolyzability" refers to the property of generating silanol groups by reaction with water.
[0081] As the alkoxysilane, there can be mentioned tetraalkoxysilane and a silicon compound represented by the following formula (2).
[0082]
[0083] In formula (2), R a represents a hydrogen atom or a non-hydrolyzable organic group, R b represents a hydrolyzable group. q represents an integer of 1-2.
[0084] One form of tetraalkoxysilane is represented by the following formula: Si(OR)4 (wherein, four Rs each independently represent an alkyl group having 1 to 6 carbon atoms). Examples of tetraalkoxysilane include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, tetrabutoxysilane, etc., preferably tetramethoxysilane and tetraethoxysilane. In these tetraalkoxysilanes, the alkoxy moiety may be partially hydrolyzed, and the hydrolyzed moiety may be further condensed.
[0085] As one embodiment of the alkoxysilane, a silicon compound represented by the following formula (2) can be mentioned.
[0086]
[0087] In formula (2), R a represents a hydrogen atom or a non-hydrolyzable organic group, R b represents a hydrolyzable group. q represents an integer of 1-2.
[0088] In this specification, "hydrolyzable" means a property of generating a silanol group by reaction with water.
[0089] As R a The non-hydrolyzable organic group includes: alkyl groups having 1 to 10 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, tert-pentyl (1,1-dimethylpropyl), 1,1-dimethyl-3,3-dimethylbutyl, heptyl, octyl, nonyl, and decyl; cycloalkyl groups having 3 to 10 carbon atoms, such as cyclopentyl and cyclohexyl; aromatic groups having 6 to 15 carbon atoms, such as phenyl, naphthyl, and anthracenyl; and the like.
[0090] As R b Examples of the hydrolyzable group include alkoxy groups having 1 to 5 carbon atoms, such as methoxy, ethoxy, and propoxy.
[0091] q represents an integer of 1 to 2, and is preferably 1.
[0092] In the silicon compound represented by the formula (2), the hydrolyzable group may be hydrolyzed and may be further condensed in the hydrolyzed portion.
[0093] Examples of the silicon compound represented by formula (2) include silicon compounds wherein q is 1 such as methyltrimethoxysilane, methyltriethoxysilane, methyltripropoxysilane, methyltriisopropoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, and the like; and silicon compounds wherein q is 2 such as dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, methylphenyldimethoxysilane, and the like.
[0094] Examples of the condensate of alkoxysilane include siloxane compounds obtained by partially hydrolyzing the alkoxy groups in the above tetraalkoxysilane and the silicon compound represented by the above formula (2) and condensing the hydrolyzed parts. In the condensate of alkoxysilane, the alkoxy sites may be further partially hydrolyzed, and the hydrolyzed parts may be further condensed.
[0095] As one embodiment of the condensate of tetraalkoxysilane, a silicon compound having a structure represented by the following general formula (1) can be mentioned.
[0096] General formula (1)
[0097]
[0098] (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms. n is an integer of 2 to 1000, and in one embodiment, n is 2 to 100.)
[0099] Examples of R of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, tert-amyl (1,1-dimethylpropyl), 1,1-dimethyl-3,3-dimethylbutyl, and heptyl. Preferred examples include methyl, ethyl, and butyl, and more preferred examples include methyl and ethyl.
[0100] In the above formula (1), n represents an integer of 2 to 1000, preferably n is 2 to 100, more preferably n is 3 to 50, and even more preferably n is 3 to 30.
[0101] The weight average molecular weight of the silicon compound having a structure represented by the above general formula (1) is preferably 170 to 500,000, more preferably 170 to 30,000, more preferably 200 to 10,000, more preferably 240 to 8,000, and more preferably 240 to 5,000.
[0102] In the silicon compound having a structure represented by the general formula (1), the alkoxy site may be partially hydrolyzed, and the hydrolyzed site may be further condensed.
[0103] Examples of commercially available products of alkoxysilane condensates include Methyl Silicate 51, Methyl Silicate 53A, Ethyl Silicate 40, Ethyl Silicate 48, and EMS-485 (all manufactured by Colcoat Corporation).
[0104] Moreover, among the alkoxysilane condensates, commercially available products of the hydrolysis condensate of methyl silicate include, for example, MS51, MS56, MS57, and MS56S (all manufactured by Mitsubishi Chemical Corporation).
[0105] Moreover, among the alkoxysilane condensates, commercially available products of the hydrolysis condensate of ether silicate include, for example, HAS-1, HAS-6, and HAS-10 (all manufactured by Colcoat Corporation).
[0106] The inorganic particle dispersion may contain only one alkoxysilane or two or more alkoxysilanes. In addition, the alkoxysilane and its condensate may be contained separately or both. As a preferred inorganic particle dispersion, a condensate containing alkoxysilane may be cited. Specifically, the aforementioned silicon compound having a structure represented by the following general formula (1) may be cited.
[0107] General formula (1)
[0108]
[0109] (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms. n is an integer of 2 to 1000, and in one embodiment, n is 2 to 100.)
[0110] Such an inorganic fine particle dispersion has a more excellent coating film strength.
[0111] <Ratio of the weight of SiO2 contained in alkoxysilane to the weight of inorganic fine particles>
[0112] In the inorganic particle dispersion of the present invention, as the lower limit of the weight of SiO contained in the alkoxysilane relative to the weight of the inorganic particles ([SiO contained in the alkoxysilane Weight] / [weight of inorganic particles]), preferably greater than 0.10, more preferably more than 0.20, more preferably more than 0.29, more preferably more than 0.40, more preferably more than 0.50, more preferably more than 0.60, more preferably more than 0.70. As the upper limit, preferably 10.00 or less, more preferably 7.00 or less, more preferably 5.00 or less, more preferably 3.00 or less, more preferably 2.50 or less, more preferably 2.00 or less, more preferably 1.50 or less, more preferably 1.40 or less, more preferably 1.30 or less, more preferably 1.20 or less.
[0113] [Pore-forming agent]
[0114] The inorganic particle dispersion of the present invention contains a pore former. As described later, in the present invention, a substrate having an inorganic particle layer formed on the surface is formed through a coating step using an inorganic particle dispersion and a dispersion medium removal step. The inorganic particle layer contains a pore former in advance, and in the subsequent heat treatment step, the pore former contained in the inorganic particle layer is thermally decomposed and removed, so that pores can be given to the inorganic particle layer. Since the inorganic particle layer has pores from the pore former and interparticle spaces between the inorganic particles, it becomes a layer with a low refractive index. This is conducive to improving light transmittance.
[0115] As one form of the pore-forming agent, organic ammonium salts, pyridine Salts are preferably organic ammonium salts. Preferred examples include organic ammonium salts having a structure represented by the following general formula (3).
[0116] General formula (3)
[0117]
[0118] (In the formula, each of L1 to L4 independently represents a hydrogen atom or an organic group having 1 to 15 carbon atoms, and the total number of carbon atoms contained in the organic groups in L1 to L4 is 1 to 40. E1 represents a monovalent anion.)
[0119] In the general formula (3), each of L1 to L4 independently represents a hydrogen atom or an organic group having 1 to 15 carbon atoms. Specific examples of the organic group having 1 to 15 carbon atoms include: alkyl groups having 1 to 15 carbon atoms such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tetradecyl, benzyl, 2-hydroxyethyl, 3-chloro-2-hydroxypropyl, and 2-chloroethyl; cycloalkyl groups having 3 to 10 carbon atoms such as cyclopentyl and cyclohexyl; aromatic groups having 6 to 15 carbon atoms such as phenyl; and the like.
[0120] In the general formula (3), E1 represents a monovalent anion. Specific examples of E1 include halide ions (fluoride ions, chloride ions, bromide ions, iodide ions), hydrogen sulfate ions, nitrate ions, bis(trifluoromethanesulfonyl)imide ions, bis(fluorosulfonyl)imide ions, p-toluenesulfonate ions, hexafluorophosphate ions, and tetrafluoroborate ions, preferably chloride ions, bromide ions, and hydrogen sulfate ions, more preferably chloride ions and bromide ions, and more preferably chloride ions.
[0121] As the organic ammonium salt having a structure represented by the general formula (3), preferably secondary ammonium salts, tertiary ammonium salts, and quaternary ammonium salts are mentioned, more preferably tertiary ammonium salts and quaternary ammonium salts are mentioned, and more preferably quaternary ammonium salts are mentioned. Specific examples of quaternary ammonium salts include the following. Tetramethylammonium chloride, trimethyltetradecylammonium chloride, n-octyltrimethylammonium chloride, decyltrimethylammonium chloride, tetraethylammonium chloride, benzyltrimethylammonium chloride, trimethylphenylammonium chloride, benzyltributylammonium chloride, bis(2-hydroxyethyl)dimethylammonium chloride, triethylmethylammonium chloride, (3-chloro-2-hydroxypropyl)trimethylammonium chloride, (2-chloroethyl)trimethylammonium chloride, 2-hydroxypropyltrimethylammonium chloride, tributylmethylammonium chloride, (2-methoxyethoxymethyl)triethylammonium chloride, benzyldimethylphenylammonium chloride, tetrabutylammonium chloride, tetrapropylammonium chloride, dodecyltrimethylammonium chloride, diallyldimethylammonium chloride, dodecyltrimethylammonium chloride, benzyltriethylammonium chloride, (2-hydroxyethyl)trimethylammonium chloride, trimethylpropyl bromide ammonium, tetramethylammonium bromide, 2-bromoethyltrimethylammonium bromide, n-octyltrimethylammonium bromide, trimethylphenylammonium bromide, hexyldimethyloctylammonium bromide, hexyltrimethylammonium bromide, (3-bromopropyl)trimethylammonium bromide, benzyltriethylammonium bromide, butyltrimethylammonium bromide, tetrahexylammonium bromide, tetrapentylammonium bromide, trimethylnonylammonium bromide, benzyltrimethylammonium bromide, (2-hydroxyethyl)trimethylammonium bromide, tetradecyltrimethylammonium bromide, tetraethylammonium bromide, dodecyltrimethylammonium bromide, decyltrimethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, dimethyldioctylammonium bromide, benzyltributylammonium bromide, tetra(decyl)ammonium bromide, tetraheptylammonium bromide, tetra-n-octylammonium bromide, didecyldimethylammonium bromide, didodecyldimethylammonium bromide.
[0122] In the general formula (3), each of L1 to L4 independently represents a hydrogen atom or an organic group having 1 to 15 carbon atoms. The preferred carbon number of the organic group in L1 to L4 is preferably 1 to 12 carbon atoms, more preferably 1 to 10 carbon atoms, more preferably 1 to 8 carbon atoms, more preferably 1 to 7 carbon atoms, and more preferably 1 to 4 carbon atoms. When such an organic group is used, good coating properties can be exhibited.
[0123] In the general formula (3), the total number of carbon atoms of the organic groups contained in L1 to L4 is 1 to 40.
[0124] The total number of carbon atoms of the organic groups in L1 to L4 is preferably 1 to 32, more preferably 1 to 26, more preferably 1 to 24, more preferably 1 to 18, more preferably 4 to 18, more preferably 4 to 16, more preferably 4 to 14, more preferably 4 to 13, more preferably 4 to 12, more preferably 4 to 11, more preferably 4 to 10, more preferably 8 to 11. Such a total number of carbon atoms of the organic groups in L1 to L4 can exhibit good coating properties.
[0125] <Ratio of the weight of the pore former to the total weight of SiO2 contained in the alkoxysilane>
[0126] In the inorganic fine particle dispersion of the present invention, the weight of the pore-forming agent relative to the total weight of SiO contained in the alkoxysilane ([weight of the pore-forming agent] / [total weight of SiO contained in the alkoxysilane]) is 0.10 or more. As a lower limit, it is preferably 0.10 or more, more preferably 0.20 or more, more preferably 0.30 or more, more preferably 0.40 or more, more preferably 0.50 or more, more preferably 0.60 or more, more preferably 0.70 or more, more preferably 1.50 or more, more preferably 1.70 or more, more preferably 2.00 or more, more preferably 2.51 or more, more preferably 2.60 or more. As an upper limit, it is preferably 8.00 or less, more preferably 5.00 or less, more preferably 4.50 or less, more preferably 4.00 or less, more preferably 3.00 or less.
[0127] As one mode of inorganic particle dispersion, from the viewpoints of smoothness of coating film, suppression of surface defects, etc., a surface conditioner may be included. In the case where the inorganic particle dispersion includes a surface conditioner, as one mode of its content, it is 0.01 parts by weight or more and 0.5 parts by weight or less relative to 100 parts by weight of the liquid dispersion medium. As a specific example of the surface conditioner, polyether-modified siloxanes etc. may be cited.
[0128] [Other ingredients]
[0129] The inorganic fine particle dispersion may contain silicon dioxide in addition to the inorganic fine particles X and the inorganic fine particles Y. The inorganic fine particle dispersion may also contain a thickener, a thixotropic agent, a defoaming agent, a light stabilizer, a pigment, an antifouling agent, an antifungal agent, a dustproofing agent, an antifreeze performance improving agent, a weathering agent, an ultraviolet stabilizer, a surfactant, etc., depending on the purpose and the method of use.
[0130] <Method for producing inorganic fine particle dispersion>
[0131] The inorganic fine particle dispersion can be prepared, for example, by the following methods, but is not limited to these methods.
[0132] Prepare a raw material liquid obtained by dispersing inorganic particles in a solvent. Liquid dispersion medium A, liquid dispersion medium B and water may be included in the raw material liquid in advance. Necessary amounts of liquid dispersion medium A, liquid dispersion medium B, water and pore formers are mixed in the raw material liquid. Surface conditioners and other components may also be added as needed. Then, an inorganic particle dispersion liquid may be prepared by adding alkoxysilane and mixing. Pore formers, surface conditioners, alkoxysilanes and other components may be used as pore formers, surface conditioners, alkoxysilanes and other components obtained by pre-dispersing in an appropriate solvent. As the solvent, liquid dispersion medium A, liquid dispersion medium B and water may be cited.
[0133] In the process of preparing the inorganic fine particle dispersion, by applying a strong dispersion method such as ultrasonic dispersion or ultrahigh pressure dispersion, the inorganic fine particles can be dispersed particularly uniformly in the inorganic fine particle dispersion.
[0134] As a preferred method for adding alkoxysilane to the inorganic particle dispersion, from the perspective of long-term stable storage and management of the coating agent, the following method can be cited: the inorganic particle dispersion is prepared in advance by separating the inorganic particle dispersion into the following agent A and agent B, and the agent A and agent B are mixed just before coating to prepare the inorganic particle dispersion.
[0135] [Agent A]: contains inorganic fine particles and water, and may appropriately contain liquid dispersion medium A, liquid dispersion medium B, a pore former, and other components.
[0136] [Agent B]: contains alkoxysilane, and may appropriately contain liquid dispersion medium A, liquid dispersion medium B, water, a pore former, and other components.
[0137] The agent A contains inorganic fine particles and water, and may contain a liquid dispersion medium A, a liquid dispersion medium B, a pore former, and other components as appropriate.
[0138] When the total weight of Agent A is 100 mass %, the content of inorganic fine particles contained in Agent A is preferably 0.2 mass % to 30 mass %, more preferably 0.3 mass % to 20 mass %, and further preferably 0.5 mass % to 15 mass %.
[0139] When the total weight of Agent A is set to 100% by mass, as the lower limit of the water content contained in Agent A, it is preferably 1% by mass or more of water, more preferably 5% by mass or more of water, more preferably 10% by mass or more of water, and more preferably 15% by mass or more of water.
[0140] In addition, as the upper limit of the water content contained in Agent A, it is preferably 90% by mass or less of water, more preferably 80% by mass or less of water, more preferably 60% by mass or less of water, more preferably 50% by mass or less of water, more preferably 40% by mass or less of water, and more preferably 30% by mass or less of water.
[0141] The agent B contains alkoxysilane and may contain liquid dispersion medium A, liquid dispersion medium B, water, a pore former, and other components as appropriate. Alternatively, the agent B may use only alkoxysilane as the agent B.
[0142] The water content in Agent B is preferably small. When the total weight of Agent B is set to 100% by weight, the water content in Agent B is preferably 5% by weight or less, more preferably 3% by weight or less, more preferably 1% by weight or less, and particularly preferably 0.8% by weight or less.
[0143] [Method for producing laminated body]
[0144] A laminate comprising a substrate and an inorganic particle layer can be obtained by a method comprising the following steps: a step of coating an inorganic particle dispersion on a substrate (coating step); then a step of removing the liquid dispersion medium from the inorganic particle dispersion coated on the substrate by an appropriate method to form an inorganic particle layer (hereinafter sometimes referred to as a "coating film") on the substrate (dispersion medium removal step); and a step of heat treating the substrate and the inorganic particle layer (heat treatment step).
[0145] <Coating process>
[0146] The method for coating the inorganic fine particle dispersion on the substrate is not particularly limited, and examples thereof include gravure coating, reverse coating, roll coating, spray coating, kiss coating, die coating, dip coating, and bar coating.
[0147] As the substrate, plastic films or sheets, glass plates can be cited. As specific examples of plastic films or sheets, films or sheets of polyethylene terephthalate, polyethylene, polypropylene, cellophane, triacetyl cellulose, diacetyl cellulose, acetyl cellulose butyrate, polymethyl methacrylate, polycarbonate, polystyrene, MS resin, SAN resin, silicone resin, etc. can be cited. In addition, optical components such as polarizing plates, diffusion plates, light guide plates, brightness enhancement films, and reflective polarizing plates can be used as substrates. The substrate can have a hard coating layer containing ultraviolet curable resins, etc., and an antistatic layer containing conductive particles, etc. as a surface layer. As a preferred material of the substrate, glass can be cited.
[0148] When glass is used as the substrate, there are no particular restrictions on the composition and manufacturing method of the glass that can be used. Soda glass, crystal glass, borosilicate glass, quartz glass, aluminosilicate glass, borate glass, phosphate glass, alkali-free glass, composite glass with ceramics, etc. can be used.
[0149] Before applying the inorganic fine particle dispersion on the substrate, the surface of the substrate may be subjected to pretreatment such as corona treatment, ozone treatment, plasma treatment, flame treatment, electron beam treatment, anchor coating treatment, cleaning treatment, etc.
[0150] <Dispersion medium removal step>
[0151] By removing the liquid dispersion medium (liquid dispersion medium A, liquid dispersion medium B and water) from the inorganic particle dispersion liquid coated on the substrate surface (dispersion medium removal process), an inorganic particle layer can be formed on the substrate surface. The removal of the liquid dispersion medium can be carried out by, for example, heating under normal pressure or under reduced pressure after natural drying at room temperature.
[0152] The pressure and heating temperature when removing the liquid dispersion medium can be appropriately selected according to the material used. For example, the drying can be generally performed at 50°C to 120°C, preferably at about 60°C to 110°C. In one embodiment, the drying can be performed at 50°C to 80°C, and in another embodiment, the drying can be performed at 20°C to 50°C.
[0153] <Heat treatment process>
[0154] After the liquid dispersion medium is removed by the above-mentioned drying, the substrate having an inorganic particle layer formed on the surface may be heat treated (heat treatment process). Through the heat treatment process, the pore-forming agent contained in the inorganic particle layer is thermally decomposed and removed to give holes to the inorganic particle layer, and the light transmittance can be improved. At the same time, the adhesion between the substrate and the inorganic particle layer can also be improved by the heat treatment process. There is no particular limitation on the heat treatment method, and local heating of the inorganic particle layer by heating in an oven, electromagnetic wave irradiation, etc. can be cited. In the heat treatment process, the heat treatment temperature is preferably 200°C or more and 800°C or less, more preferably 300°C or more and 800°C or less, more preferably 400°C or more and 800°C or less, more preferably 500°C or more and 750°C or less. The atmosphere during heating is preferably an oxygen-containing gas atmosphere, preferably air. The heating time is preferably 10 minutes or less.
[0155] In one embodiment of the inorganic fine particle dispersion of the present invention, the inorganic fine particle dispersion may be applied to the glass substrate before the quenching step in the manufacture of the glass substrate, or the glass substrate coated with the inorganic fine particle dispersion may be quenched as it is.
[0156] <Other components>
[0157] In one embodiment of the inorganic particle dispersion and the laminate of the present invention, from the viewpoint of anti-reflection characteristics, a resin anti-reflection film can be used in the substrate used, or an inorganic particle layer and a resin anti-reflection film layer can be introduced into the laminate. The structure of the laminate having both an inorganic particle layer and a resin anti-reflection film layer is arbitrary, and an inorganic particle layer can be arranged on one side of the substrate and a resin anti-reflection film layer can be arranged on the other side. The inorganic particle layer can be arranged on the substrate and then the resin anti-reflection film layer can be arranged, or the inorganic particle layer can be arranged on the substrate and then the resin anti-reflection film layer can be arranged.
[0158] [Laminated body]
[0159] In one embodiment, the inorganic particle layer of the laminated body including the substrate and the inorganic particle layer obtained by the above method has an anti-reflection function. The thickness of the inorganic particle layer is not particularly limited. In one embodiment, the thickness of the inorganic particle layer is more than 40nm and less than 300nm, in another embodiment, the thickness of the inorganic particle layer is more than 50nm and less than 240nm, in addition, in another embodiment, the thickness of the inorganic particle layer is more than 50nm and less than 220nm, in addition, in another embodiment, the thickness of the inorganic particle layer is more than 80nm and less than 200nm, in another embodiment, the thickness of the inorganic particle layer is more than 50nm and less than 150nm, in another embodiment, the thickness of the inorganic particle layer is more than 80nm and less than 130nm.
[0160] The thickness of the inorganic particle layer is preferably 50 nm to 240 nm, more preferably 50 nm to 220 nm, further preferably 80 nm to 200 nm, and particularly preferably 90 nm to 150 nm. The thickness of the inorganic particle layer can be adjusted by changing the solid content in the inorganic particle dispersion and the coating amount of the inorganic particle dispersion.
[0161] The present invention discloses the following second inventions
[10] to
[20] . According to the second invention of the present invention, a laminate having a layer excellent in antifouling properties and coating film adhesion even on a substrate having a light transmittance of substantially 0% can be provided.
[0162]
[10] A laminate, wherein the laminate is obtained by coating an inorganic particle dispersion on a substrate having a light transmittance of substantially 0%, the inorganic particle dispersion comprising: inorganic particles, a liquid dispersion medium A having a boiling point greater than 121°C and less than 190°C, a liquid dispersion medium B having a boiling point less than 100°C, and water, wherein when the total amount of the inorganic particle dispersion is set to 100% by mass, the content of the liquid dispersion medium A is greater than or equal to 0.5% by mass and less than 15% by mass.
[0163]
[11] The laminate according to
[10] , wherein the inorganic fine particle dispersion further contains alkoxysilane.
[0164]
[12] The laminate according to
[10] or
[11] , wherein the substrate having a light transmittance of substantially 0% is a metal substrate.
[0165]
[13] A laminate as described in
[11] or
[12] , wherein in the inorganic particle dispersion, the ratio of the weight of SiO2 contained in the alkoxysilane to the weight of the inorganic particles ([the weight of SiO2 contained in the alkoxysilane] / [the weight of the inorganic particles]) is greater than 0.10.
[0166]
[14] The laminate according to any one of
[11] to
[13] , wherein the alkoxysilane has a structure represented by the following general formula (1).
[0167] General formula (1)
[0168]
[0169] (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms. n is an integer of 2 to 1000.)
[0170]
[15] The laminate according to any one of
[10] to
[15] , wherein the inorganic fine particles are inorganic fine particles containing silica particles.
[0171]
[16] The laminate according to
[11] , wherein the inorganic fine particle dispersion contains a pore former.
[0172]
[17] The laminate according to
[16] , wherein the pore former is an organic ammonium salt.
[0173]
[18] A laminate as described in
[16] or
[17] , characterized in that in the inorganic fine particle dispersion, the ratio of the weight of the pore-forming agent to the total weight of SiO2 contained in the alkoxysilane ([weight of the pore-forming agent] / [total weight of SiO2 contained in the alkoxysilane]) is greater than 0.10.
[0174]
[19] A method for manufacturing a laminate as described in
[10] , wherein the method for manufacturing a laminate comprises: a step of coating an inorganic particle dispersion on a substrate (coating step); and a step of removing liquid dispersion medium A, liquid dispersion medium B and water from the inorganic particle dispersion coated on the substrate to form an inorganic particle layer on the substrate (dispersion medium removal step).
[0175]
[20] The method for producing a laminate as described in
[19] , wherein the method for producing a laminate further comprises a heat treatment step after the dispersion medium removal step. In the second invention, the inorganic particles other than the substrate, the liquid dispersion medium A having a boiling point greater than 121°C and less than 190°C, the liquid dispersion medium B having a boiling point less than 100°C, water, alkoxysilane, pore-forming agent, inorganic particle dispersion liquid, the method for producing the inorganic particle dispersion liquid, the method for producing the laminate, the laminate, etc. can be the same as those described above, and can be used and produced under the same conditions as those described above.
[0176] In the second invention, by coating the above-mentioned inorganic particle dispersion on a substrate having a light transmittance of substantially 0%, a laminate having a layer with excellent antifouling properties and film adhesion can be provided. "Coating" herein refers to a process (coating process) comprising coating the inorganic particle dispersion on a substrate, followed by a process (dispersion medium removal process) of removing a liquid dispersion medium from the inorganic particle dispersion coated on the substrate by an appropriate method to form a coating. It should be noted that the heat treatment process in the manufacturing method of the laminate can be appropriately omitted according to the heat resistance of the substrate used.
[0177] As the substrate used in the second invention, from the viewpoint of light-shielding in the use of building materials, etc., a substrate having a light transmittance of substantially 0% can be cited. It should be noted that the light transmittance of substantially 0% here means that the average value of the total light transmittance value in the region with a wavelength of more than 380nm and less than 1100nm in the total light transmittance spectrum measurement is less than 1%. The substrate can be a substrate containing a material having a light transmittance of substantially 0%, or a substrate to which a component having a light transmittance of substantially 0% is added or coated to a transparent material or an opaque material. As the material of the substrate, resin materials, metal materials, and inorganic materials can be cited.
[0178] Examples of the resin material include polyethylene, polypropylene, olefin-based thermoplastic elastomers, polyvinyl chloride, polyvinylidene chloride, vinyl chloride-based thermoplastic elastomers, polystyrene, acrylonitrile-butadiene-styrene, acrylonitrile-styrene, styrene-based thermoplastic elastomers, polyester, polycarbonate, polyamide, silicone resin, polyvinyl acetal, polyacetal, polyvinyl alcohol, ethylene-vinyl alcohol resin, cellulose resin, acrylic polyol resin, polyester polyol resin, polyester-based thermoplastic elastomer, urethane resin, polyurethane-based thermoplastic elastomer, polytetrafluoroethylene, fluorine-containing resin, polyvinyl acetate, ethylene-vinyl acetate, methyl (meth)acrylate polymer, ethyl (meth)acrylate polymer, octadecyl (meth)acrylate polymer, hexadecyl (meth)acrylate polymer, tetradecyl (meth)acrylate polymer, polymethyl methacrylate, polymethyl acrylate, acrylonitrile-acrylic rubber-styrene resin , acrylonitrile-ethylene rubber-styrene resin, (meth)acrylate-styrene resin, styrene-butadiene-styrene resin, styrene-butadiene copolymer, polyphenylene ether, modified polyphenylene ether, polydiphenyl ether, polyphenylene sulfide, polyamide-imide, polyetheretherketone, polyether-polypropylene block copolymer, polyetheresteramide, ethylene-methyl (meth)acrylate copolymer, ethylene-ethyl (meth)acrylate copolymer, ethylene-octadecyl (meth)acrylate copolymer, ethylene-hexadecyl (meth)acrylate copolymer, ethylene-tetradecyl (meth)acrylate copolymer, ethylene-octadecyl (meth)acrylate-methyl (meth)acrylate copolymer and other ethylene-(meth)acrylate copolymers, epoxy resins, phenolic resins, xylene resins, petroleum resins, urea resins, melamine resins, alkyd resins, furan resins, polyimides, unsaturated polyester resins, DAP resins, polyurethanes, silicone resins, thermosetting acrylic resins, etc.
[0179] Examples of the inorganic material include glass, quartz, calcium silicate, gypsum, concrete, and ALC boards.
[0180] Examples of the metal material include aluminum, aluminum alloys, iron, galvanized steel, galvanized steel, stainless steel, and tinplate.
[0181] Preferred materials for the substrate among the above include metal materials and inorganic materials from the viewpoint of coating film adhesion.
[0182] Before applying the inorganic fine particle dispersion onto a substrate used in the laminate, the surface of the substrate may be subjected to pretreatment such as corona treatment, ozone treatment, plasma treatment, flame treatment, electron beam treatment, anchor coating treatment, cleaning treatment, etc.
[0183] The present invention discloses the following third inventions
[21] to
[31] . According to the third invention, a laminate having a coating film structure with higher light transmittance and excellent antifouling properties can be provided.
[0184]
[21] A laminate comprising a substrate and a coating applied on at least one of its main surfaces, wherein the coating comprises a smooth layer and a porous layer, the smooth layer being present on the outermost side of the coating, the smooth layer containing silicon dioxide, the smooth layer having a thickness of 5 nm to 50 nm, the surface roughness Sa of the outer surface of the smooth layer being less than 4.70 nm, the porous layer being present between the smooth layer and the substrate, the porous layer containing silicon dioxide, the porous layer having a thickness of 60 nm to 200 nm, and the kurtosis of the brightness distribution of the cross section of the porous layer in a scanning electron microscope photograph being less than 0.320.
[0185]
[22] A laminate as described in
[21] , wherein the laminate is obtained by coating an inorganic particle dispersion, the inorganic particle dispersion comprising: inorganic particles, a liquid dispersion medium A having a boiling point greater than 121°C and less than 190°C, a liquid dispersion medium B having a boiling point less than 100°C, water, alkoxysilane, and a pore-forming agent, and when the total amount of the inorganic particle dispersion is set to 100% by mass, the content of the liquid dispersion medium A is greater than or equal to 0.5% by mass and less than 15.0% by mass.
[0186]
[23] The laminate according to
[22] , wherein the primary particle size of the inorganic fine particles is greater than or equal to 1 nm and less than 30 nm.
[0187]
[24] A laminate as described in
[22] or
[23] , wherein in the inorganic particle dispersion, the ratio of the weight of SiO2 contained in the alkoxysilane to the weight of the inorganic particles ([the weight of SiO2 contained in the alkoxysilane] / [the weight of the inorganic particles]) is greater than 0.10.
[0188]
[25] The laminate according to any one of
[22] to
[24] , wherein the alkoxysilane has a structure represented by the following general formula (1).
[0189] General formula (1)
[0190]
[0191] (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms. n is an integer of 2 to 1000).
[0192]
[26] The laminate according to any one of
[22] to
[25] , wherein the inorganic fine particles are inorganic fine particles containing silica particles.
[0193]
[27] The laminate according to any one of
[22] to
[26] , wherein the pore former is an organic ammonium salt.
[0194]
[28] A laminate as described in any one of
[22] to
[27] , characterized in that in the inorganic fine particle dispersion, the ratio of the weight of the pore-forming agent to the total weight of SiO2 contained in the alkoxysilane ([weight of the pore-forming agent] / [total weight of SiO2 contained in the alkoxysilane]) is greater than 0.10.
[0195]
[29] A laminate as described in any one of
[21] to
[28] , wherein the laminate is manufactured by the following steps: a step of coating an inorganic particle dispersion on a substrate (coating step); and a step of removing liquid dispersion medium A, liquid dispersion medium B and water from the inorganic particle dispersion coated on the substrate to form an inorganic particle layer on the substrate (dispersion medium removal step).
[0196]
[30] The laminate according to
[29] , wherein the laminate is produced by a production method further comprising a heat treatment step after the dispersion medium removal step.
[0197]
[31] The laminate according to
[29] or
[30] , wherein the coating step is performed once.
[0198] In the third invention, the substrate, silica, inorganic particles, a liquid dispersion medium A having a boiling point greater than 121°C and less than 190°C, a liquid dispersion medium B having a boiling point less than 100°C, water, alkoxysilane, a pore-forming agent, an inorganic particle dispersion, a method for producing an inorganic particle dispersion, a method for producing a laminate, a laminate, etc. can be the same as described above, and can be used and manufactured under the same conditions as described above.
[0199] In the third invention, by coating the inorganic particle dispersion on a substrate, a laminate having a coating structure with higher light transmittance and excellent antifouling properties can be provided. The "coating" herein refers to a process comprising a step of coating the inorganic particle dispersion on a substrate (coating process), followed by a process of removing a liquid dispersion medium from the inorganic particle dispersion coated on the substrate by an appropriate method to form a coating (dispersion medium removal process).
[0200] In the third invention, the coating film applied on at least one side of the main surface of the substrate comprises a smooth layer and a porous layer. The smooth layer is present on the outermost side of the coating film, contains silicon dioxide, and has a thickness of 5 nm to 50 nm.
[0201] The content of silicon dioxide in the smooth layer is preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, and more preferably 90% by mass or more.
[0202] The smooth layer is formed by silicon dioxide mainly derived from the alkoxysilane component in the inorganic particle dispersion, and in a cross-sectional photograph taken using a scanning electron microscope (SEM) observation method described later, contains substantially no voids between the inorganic particles. In the cross-sectional photograph, the layer has an insufficient difference in brightness between the light and dark portions compared to the porous layer described below.
[0203] The preferred thickness of the smooth layer is 7 nm to 50 nm, more preferably 10 nm to 50 nm, more preferably 10 nm to 40 nm, more preferably 15 nm to 40 nm, more preferably 15 nm to 30 nm, and more preferably 15 nm to 25 nm. When the thickness is such, good antifouling properties are exhibited.
[0204] The surface roughness Sa of the outer surface of the smooth layer is 4.70 nm or less. The surface roughness Sa of the outer surface is preferably 4.00 nm or less, more preferably 3.00 nm or less, more preferably 2.00 nm or less, more preferably 1.75 nm or less, more preferably 1.50 nm or less, more preferably 1.30 nm or less, more preferably 1.20 nm or less, more preferably 1.10 nm or less, more preferably 1.00 nm or less, more preferably 0.90 nm or less. When the surface roughness Sa of the outer surface is such, good antifouling properties are exhibited.
[0205] The porous layer exists between the smooth layer and the substrate, contains silicon dioxide, and has a thickness of 60 nm to 200 nm.
[0206] The content of silicon dioxide in the porous layer is preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, and more preferably 90% by mass or more. When the content is such, the light transmittance is excellent.
[0207] The preferred thickness of the porous layer is 60nm to 200nm, more preferably 60nm to 190nm, more preferably 60nm to 180nm, more preferably 60nm to 170nm, more preferably 60nm to 160nm, more preferably 70nm to 160nm, more preferably 80nm to 160nm, more preferably 90nm to 160nm, more preferably 100nm to 160nm, more preferably 110nm to 160nm, more preferably 110nm to 150nm, more preferably 110nm to 145nm. When it is such a thickness, the light transmittance is excellent.
[0208] The porous layer has inorganic particles and gaps from the gaps between inorganic particles in the cross-sectional photo of the method observed by a scanning electron microscope (SEM) described later, so the porous layer has a concavo-convex structure in its cross-section. Thus, in the cross-sectional photo of the method observed by a scanning electron microscope (SEM) described later, there are bright and dark parts at the same time, with a distribution of brightness. The kurtosis of the brightness distribution of the porous layer in the scanning electron microscope photo of the cross-section is less than 0.320. The kurtosis of the brightness distribution in the scanning electron microscope photo of the cross-section can be obtained by the method described later. The kurtosis of the brightness distribution is preferably less than 0.300, more preferably less than 0.250, more preferably less than 0.200, more preferably less than 0.150, more preferably less than 0.130, more preferably less than 0.130, more preferably less than 0.120, more preferably less than 0.110, more preferably less than 0.100, more preferably less than 0.090, more preferably less than 0.060. When the peak degree of the brightness distribution is as described above, it is a good porous structure and has excellent light transmittance.
[0209] In the third invention, when manufacturing a laminated body, the step of applying the inorganic fine particle dispersion on the substrate (coating step) is preferably performed once. By performing the step once, the labor of the step can be saved.
[0210] Example
[0211] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0212] The main materials used are described below.
[0213] [Base material]
[0214] Glass substrate (transmittance: 88.6%; width: 26 mm, length: 76 mm, thickness: 1.3 mm) The above glass substrate is referred to as substrate-1.
[0215] The transmittance value of the slide glass used as the substrate is measured by the method described in the section "Spectral transmittance" in the following Examples.
[0216] [Inorganic particles]
[0217] The following dispersion liquid was used as the inorganic fine particles.
[0218] Particle-1 (inorganic fine particles Y): Snowtex (registered trademark) ST-OUP (manufactured by Nissan Chemical Industries, Ltd.; an aqueous dispersion of colloidal silica fine particle chains formed by three or more particles having a particle size of 5 nm or more and 20 nm or less connected in a chain; an average particle size of 40 nm or more and 300 nm or less as determined by a dynamic light scattering method; a solid content concentration of 15% by weight)
[0219] Particle-2 (inorganic fine particles X): Snowtex (registered trademark) ST-OXS (manufactured by Nissan Chemical Industries, Ltd.; aqueous dispersion of colloidal silica; average particle size of 4 nm to 6 nm; solid content concentration of 10% by weight)
[0220] Particle-3 (inorganic fine particles X): Snowtex (registered trademark) IPA-ST (manufactured by Nissan Chemical Industries, Ltd.; 2-propanol dispersion of colloidal silica; average particle size 12 nm; solid content concentration 30% by weight)
[0221] Particle-4 (inorganic fine particles X): Snowtex (registered trademark) ST-O (manufactured by Nissan Chemical Industries, Ltd.; aqueous dispersion of colloidal silica; average particle size 12 nm; solid content concentration 20% by weight)
[0222] In addition, the numerical value of the addition amount of inorganic fine particles in Table 1-1 and Table 1-2 is the addition amount of the solid content concentration when the total amount of the composition (total amount of the dispersion) is 100 mass %.
[0223] [Liquid dispersion medium A]
[0224] The liquid dispersion medium A used was the following.
[0225] A-1: 3-methoxy-1-butanol (boiling point 158°C)
[0226] A-2: 3-methoxy-3-methylbutanol (boiling point 174°C)
[0227] A-3: 2-methoxyethyl acetate (boiling point 143°C)
[0228] A-4: Ethylene glycol monotert-butyl ether (boiling point 153°C)
[0229] [Liquid dispersion medium B]
[0230] B-1: Ethanol (boiling point 78°C)
[0231] B-2: Methanol (boiling point 65°C)
[0232] B-3: 2-Propanol (boiling point 83°C)
[0233] [Alkoxysilane]
[0234] C-1: MKC Silicate (registered trademark) MS51 (manufactured by Mitsubishi Chemical Corporation; polymethoxysiloxane)
[0235] C-2: γ-Glycidoxypropyltrimethoxysilane
[0236] [Pore-forming agent]
[0237] P-1: Benzyltriethylammonium chloride
[0238] [Other ingredients]
[0239] Z-1: 1-methoxy-2-propanol (boiling point 120°C)
[0240] Z-2: 1,6-diacetoxyhexane (boiling point 260°C)
[0241] Z-3: KF-6001 (manufactured by Shin-Etsu Chemical, dual-end type / methanol-modified silicone oil)
[0242] Z-4: BYK-349 (manufactured by BYK, silicone surface conditioner)
[0243] Z-5: Acetic acid
[0244] Z-6: DISPERBYK-2015 (manufactured by BYK, wetting dispersant)
[0245] Z-7: Hydrochloric acid
[0246] Z-8: Itaconic acid
[0247] Z-9: Dicyanamide
[0248] Z-10: KF-6004 (manufactured by Shin-Etsu Chemical, polyether-modified silicone oil)
[0249] Z-11: EMALEX715 (polyoxyethylene lauryl ether)
[0250] Z-12: Aluminum triacetylacetonate
[0251] The laminated bodies including the glass substrate and the inorganic fine particle layer in the examples and comparative examples were produced by the following method.
[0252] Examples 1 to 7
[0253] A mixture of inorganic fine particles, liquid dispersion medium A, liquid dispersion medium B, water, a pore former, and other components was stirred so as to have the component ratios shown in Table 1-1, and alkoxysilane was added and stirred to prepare an inorganic fine particle dispersion.
[0254] A substrate was prepared in which one side of the substrate was masked with a masking tape. Here, substrate-1 was used as the substrate.
[0255] For the above-mentioned substrate subjected to masking treatment, the prepared inorganic particle dispersion was applied to the side of the substrate that was not subjected to masking treatment using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, the masking tape was removed from the substrate and dried naturally at room temperature. For the obtained substrate, an oven was used to dry at 100°C for 3 minutes in air, and then a muffle furnace was used to heat at 700°C for 2 minutes in air, thereby forming an inorganic particle layer on the substrate, thereby obtaining a laminate comprising a substrate and an inorganic particle layer.
[0256] Examples 11 to 14
[0257] A mixture of inorganic fine particles, liquid dispersion medium A, liquid dispersion medium B, water, a pore former, and other components was stirred so as to have the component ratios listed in Table 1-1, and alkoxysilane was added and stirred to prepare an inorganic fine particle dispersion.
[0258] A substrate was prepared in which one side of the substrate was masked with a masking tape. Here, substrate-2 was used as the substrate.
[0259] A laminate including a substrate and an inorganic fine particle layer was prepared by the method of Example 1 using the above-mentioned inorganic fine particle dispersion.
[0260] Comparative Examples 1 to 4
[0261] In the mode of becoming the composition ratio of record in table 1-2, the mixture such as inorganic particles, liquid dispersion medium A, liquid dispersion medium B, water and alkoxysilane, pore former and other components are stirred, thus prepared inorganic particle dispersion liquid.Use this inorganic particle dispersion liquid, the laminated body comprising substrate and inorganic particle layer is made by the method for embodiment 1.In comparative example 1 and comparative example 2, in coating, the depression of coating film is large, produces coating badly, and the laminated body obtained is inhomogeneous.Therefore, the evaluation of coating film adhesion and antifouling property cannot be carried out.
[0262] Comparative Example 5
[0263] A dispersion containing alkoxysilane (dispersion C-H1) was prepared in the following manner. That is, B-1 (4.20 parts by mass), C-1 (5.40 parts by mass), water (10.0 parts by mass), and Z-5 (0.60 parts by mass) were mixed to prepare dispersion C-H1. An inorganic particle dispersion was prepared by mixing the prepared C-H1 (4.20 parts by mass), P-2 (20.14 parts by mass), Z-6 (2.64 parts by mass), Z-1 (31.21 parts by mass), B-1 (34.27 parts by mass), water (12.42 parts by mass), and P-1 (2.10 parts by mass). Using the inorganic particle dispersion, a laminate comprising a substrate and an inorganic particle layer was obtained by the method of Example 1.
[0264] Comparative Example 6
[0265] An inorganic particle dispersion was prepared by mixing C-H1 (4.20 parts by mass), P-2 (20.14 parts by mass), Z-6 (2.64 parts by mass), A-3 (31.21 parts by mass), B-1 (34.27 parts by mass), water (12.42 parts by mass), and P-1 (2.10 parts by mass) prepared in the same manner as above. Using the inorganic particle dispersion, a laminate comprising a substrate and an inorganic particle layer was obtained by the method of Example 1.
[0266] Comparative Example 8
[0267] B-2 (1.93 parts by mass) was mixed with C-2 (12.88 parts by mass) and stirred, and a 0.01 mol / L aqueous solution of Z-7 (3.80 parts by mass) was added dropwise to the solution, and the solution was further stirred at room temperature for 8 hours.
[0268] Then, B-2 (14.43 parts by mass), particle-3 (20.50 parts by mass), water (5.07 parts by mass), Z-1 (2.62 parts by mass), Z-8 (2.20 parts by mass), Z-9 (0.80 parts by mass), and Z-1 solution (0.78 parts by mass) containing 10% by weight of Z-10, P-1 (4.00 parts by mass) were added to the solution, and stirred at room temperature for 8 hours, thereby preparing an inorganic particle dispersion. Using the inorganic particle dispersion, a laminate comprising a substrate and an inorganic particle layer was obtained by the method of Example 1.
[0269] Comparative Example 9
[0270] A mixture was prepared by slowly adding water (10.00 parts by mass) to a mixture of B-1 (4.60 parts by mass) and C-1 (5.40 parts by mass), then adding Z-5 (0.60 parts by mass), and stirring at room temperature for 24 hours or more.
[0271] The above-mentioned mixture (1.25 parts by mass), particle-4 (7.56 parts by mass), Z-6 (0.76 parts by mass), water (15.93 parts by mass), B-1 (23.41 parts by mass), A-4 (20.83 parts by mass), Z-11 (0.08 parts by mass), Z-12 (0.17 parts by mass), P-1 (0.35 parts by mass) were mixed to prepare an inorganic particle dispersion. Using the inorganic particle dispersion, a laminate comprising a substrate and an inorganic particle layer was obtained by the method of Example 1.
[0272] Evaluations of Examples and Comparative Examples were performed by the following methods.
[0273] [Spectral transmittance]
[0274] The total light transmittance of the laminated body was measured using an ultraviolet visible near infrared spectrophotometer UV-3150 (manufactured by Shimadzu Corporation), wherein the laminated body comprises a layer, wherein the layer comprises a substrate and inorganic particles. Then, the value of the total light transmittance in the region with a wavelength of 380 nm or more and 1100 nm or less was read from the obtained total light transmittance spectrum, and the average value was calculated.
[0275] The spectral transmittance of the obtained laminate was observed to increase relative to that of the uncoated substrate. The increase in spectral transmittance is defined as follows.
[0276] [Increase in spectral transmittance (%)]
[0277] =[spectral transmittance of the laminate (%)]-[spectral transmittance of the uncoated substrate (%)]
[0278] [Coating film adhesion]
[0279] The adhesiveness of the laminate was evaluated by a cross-cut cellophane tape peeling test. Cellophane tape used was LP-24 (manufactured by Michelbon Co., Ltd.). The peeling state after performing the test on 100 1 mm squares was observed and evaluated as follows.
[0280] ○: No peeling at all
[0281] △: The number of peeled pieces is less than 10
[0282] ×: The number of peeled pieces is greater than 10
[0283] [Antifouling properties]
[0284] In the above-mentioned checkered tape peeling test, laminates in which the inorganic fine particle layer did not peel significantly and in which the adhesive of the tape did not transfer to the coating surface after the tape was peeled were judged to have good antifouling properties and were evaluated as follows.
[0285] 0: No glue transfer
[0286] △: There is local transfer of glue
[0287] ×: Adhesive transfer occurs on the entire surface
[0288]
[0289]
[0290]
[0291]
[0292] It can be seen that Examples 1 to 7 and 11 to 14 have good coating adhesion and antifouling properties in addition to a large increase in spectral transmittance. On the other hand, Comparative Examples 1 to 6 and 8 to 9 have a small increase in spectral transmittance, poor coating adhesion or antifouling properties, or are accompanied by poor coating.
[0293] Hereinafter, the second invention of the present invention will be described in more detail by way of examples and comparative examples, but the second invention of the present invention is not limited to the examples.
[0294] The main materials used are described below.
[0295] [Base material]
[0296] Glass substrate (transmittance 88.7%, width 25 mm, length 75 mm, thickness 1 mm) The above glass substrate is referred to as substrate-2.
[0297] [Base material]
[0298] Aluminum substrate (transmittance less than 0.2%, width 25 mm, length 75 mm, thickness 0.3 mm, alloy number A1100) The above aluminum substrate is referred to as substrate-3.
[0299] The transmittance value of the substrate is measured by the method described in the section [Spectral transmittance] of the following Examples.
[0300] [Inorganic particles]
[0301] As the inorganic fine particles, the following dispersion was used.
[0302] Particle-2 (inorganic fine particles X): Snowtex (registered trademark) ST-OXS (manufactured by Nissan Chemical Industries, Ltd.; aqueous dispersion of colloidal silica; average particle size of 4 nm to 6 nm; solid content concentration of 10% by weight)
[0303] Particle-3 (inorganic fine particles X): Snowtex (registered trademark) ST-O (manufactured by Nissan Chemical Industries, Ltd.; aqueous dispersion of colloidal silica; particle size 12 nm; solid content concentration 20% by weight)
[0304] In addition, the numerical value of the addition amount of inorganic fine particles in Table 1-3 is the addition amount of the solid content concentration when the total amount of the composition (total amount of the dispersion) is 100 mass %.
[0305] [Liquid dispersion medium A]
[0306] The liquid dispersion medium A used was the following.
[0307] A-2: 3-methoxy-3-methylbutanol (boiling point 174°C)
[0308] [Liquid dispersion medium B]
[0309] B-1: Ethanol (boiling point 78°C)
[0310] [Alkoxysilane]
[0311] C-1: MKC Silicate (registered trademark) MS51 (manufactured by Mitsubishi Chemical Corporation; polymethoxysiloxane)
[0312] C-100: MKC Silicate (registered trademark) MS56S (manufactured by Mitsubishi Chemical Corporation; polymethoxysiloxane)
[0313] [Pore-forming agent]
[0314] P-1: Benzyltriethylammonium chloride
[0315] [Other ingredients]
[0316] Z-4: BYK-349 (manufactured by BYK, silicone surface conditioner)
[0317] Z-700: EMALEX715 (manufactured by Japan Emulsifier, polyoxyalkylene monoalkyl ether)
[0318] Z-800: Sodium bis(2-ethylhexyl)sulfosuccinate (surfactant)
[0319] The inorganic laminates of Examples, Reference Examples, and Comparative Examples were produced by the following method.
[0320] Embodiments 8 to 10
[0321] A mixture of inorganic fine particles, liquid dispersion medium A, liquid dispersion medium B, water, a pore former, and other components was stirred to obtain the component ratios shown in Table 1-3, and alkoxysilane was added and stirred to prepare an inorganic fine particle dispersion.
[0322] For substrate-3, the prepared inorganic fine particle dispersion was applied on both sides of the substrate using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, it was naturally dried at room temperature. The obtained substrate was dried in an oven under the conditions of air / 120°C / 10 minutes to obtain an inorganic laminate.
[0323] Reference Example 1
[0324] A mixture of inorganic fine particles, liquid dispersion medium A, liquid dispersion medium B, water, a pore former, and other components was stirred to obtain the component ratios shown in Table 1-3, and alkoxysilane was added and stirred to prepare an inorganic fine particle dispersion.
[0325] A substrate was prepared in which one side of the substrate was masked with a masking tape. Here, substrate-2 was used as the substrate.
[0326] For the above-mentioned substrate subjected to masking treatment, the prepared inorganic particle dispersion was applied to the side of the substrate that was not subjected to masking treatment using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, the masking tape was removed from the substrate and naturally dried at room temperature. The obtained substrate was dried in an oven under the conditions of air / 100°C / 3 minutes to obtain a laminate.
[0327] Comparative Example 7
[0328] In the mode that becomes the composition ratio of record in table 1-3, the mixture such as inorganic particles, water and other components is stirred, and the inorganic particle dispersion liquid is prepared thereby.Use this inorganic particle dispersion liquid, the inorganic laminated body is made by the method for embodiment 8.In comparative example 7, in coating, the depression of coating film is large, and coating is poor, and the coating film of the inorganic laminated body obtained is inhomogeneous.Therefore, the evaluation of adhesive tape coating film adhesion and adhesive tape antifouling property cannot be carried out.
[0329] The evaluation tests of Examples and Comparative Examples were performed by the following methods.
[0330] [Spectral transmittance]
[0331] The total light transmittance of the laminated body was measured using an ultraviolet visible near infrared spectrophotometer UV-3150 (manufactured by Shimadzu Corporation), wherein the laminated body comprises a layer, wherein the layer comprises a substrate and inorganic particles. Then, the value of the total light transmittance in the region with a wavelength of 380 nm or more and 1100 nm or less was read from the obtained total light transmittance spectrum, and the average value was calculated.
[0332] [Tape film adhesion]
[0333] A transparent tape was pasted on the coating film, and visual verification was made as to whether the coating film was peeled off together with the transparent tape when the transparent tape was peeled off, thereby evaluating the adhesion of the coating film. The transparent tape used was LP-24 (manufactured by Michelbon Co., Ltd.). The peeling state of the coating film after the test was observed and evaluated in the following manner.
[0334] ○: No peeling at all
[0335] △: Some peeling
[0336] ×: The entire surface is peeled off
[0337] [Tape antifouling properties]
[0338] In the above-mentioned tape coating adhesion test, laminates without significant peeling of the inorganic fine particle layer and without transfer of the tape adhesive to the coating surface after the tape peeling were judged to have good antifouling properties and were evaluated as follows.
[0339] 0: No glue transfer
[0340] △: There is local transfer of glue
[0341] ×: The entire surface has adhesive transfer
[0342] [Ink antifouling properties]
[0343] A carbon dispersion containing 1 wt% of hydrophobic carbon and 99 wt% of liquid paraffin was prepared to prepare the contamination component. About 0.5 ml of the carbon dispersion was dripped onto the inorganic laminate or laminate after spraying water with a sprayer using a dropper. Next, the coated plate to which the carbon dispersion was dripped was made vertical, and water was sprayed with a sprayer within 10 seconds, and the spraying was continued with an upper limit of 30 seconds until the dirt stopped flowing. The appearance of the coated plate surface after the test was visually evaluated according to the following standards.
[0344] ○: Pollutants are completely removed
[0345] △: Contamination components remain on part of the coating surface
[0346] ×: Pollution components are clearly observed
[0347]
[0348] Hereinafter, the third invention of the present invention will be described in more detail by way of examples and comparative examples, but the third invention of the present invention is not limited to the examples.
[0349] The main materials used are described below.
[0350] [Base material]
[0351] Glass substrate (transmittance: 88.6%; width 26 mm, length 76 mm, thickness 1.3 mm). The above glass substrate is referred to as substrate-1. Glass substrate (transmittance 88.7%, width 25 mm, length 75 mm, thickness 1 mm). The above glass substrate is referred to as substrate-2.
[0352] The transmittance value of the slide glass used as the substrate is measured by the method described in the section [Spectral transmittance] of the following Examples.
[0353] [Inorganic particles]
[0354] The following dispersion liquid was used as the inorganic fine particles.
[0355] Particle-1 (inorganic fine particles Y): Snowtex (registered trademark) ST-OUP (manufactured by Nissan Chemical Industries, Ltd.; an aqueous dispersion of colloidal silica fine particle chains formed by three or more particles having a particle size of 5 nm or more and 20 nm or less connected in a chain; an average particle size of 40 nm or more and 300 nm or less as determined by a dynamic light scattering method; a solid content concentration of 15% by weight)
[0356] Particle-2 (inorganic fine particles X): Snowtex (registered trademark) ST-OXS (manufactured by Nissan Chemical Industries, Ltd.; aqueous dispersion of colloidal silica; average particle size of 4 nm to 6 nm; solid content concentration of 10% by weight)
[0357] Particle-5 (inorganic fine particles X): Quatron (registered trademark) PL-3 (manufactured by Fuso Chemical Industry Co., Ltd.; aqueous dispersion of silicon dioxide; primary particle size 35 nm; solid content concentration 20% by weight)
[0358] In addition, the numerical value of the addition amount of inorganic fine particles in Table 1-4 and Table 1-5 is the addition amount of the solid content concentration when the total amount of the composition (total amount of the dispersion) is 100 mass %.
[0359] [Liquid dispersion medium A]
[0360] The liquid dispersion medium A used was the following.
[0361] A-1: 3-methoxy-1-butanol (boiling point 158°C)
[0362] A-2: 3-methoxy-3-methylbutanol (boiling point 174°C)
[0363] A-5: 2-ethoxyethanol (boiling point 135.6°C)
[0364] [Liquid dispersion medium B]
[0365] B-1: Ethanol (boiling point 78°C)
[0366] B-3: 2-Propanol (boiling point 83°C)
[0367] [Alkoxysilane]
[0368] C-1: MKC Silicate (registered trademark) MS51 (manufactured by Mitsubishi Chemical Corporation; polymethoxysiloxane)
[0369] C-3: Tetraethoxysilane
[0370] [Pore-forming agent]
[0371] P-1: Benzyltriethylammonium chloride
[0372] P-2: Polyoxyethylene polyoxypropylene glycol
[0373] [Other ingredients]
[0374] Z-4: BYK-349 (manufactured by BYK, silicone surface conditioner)
[0375] Z-13: Nitric Acid
[0376] Z-14: Aluminum chloride hexahydrate
[0377] The laminated bodies including the glass substrate and the inorganic fine particle layer of the Examples and Comparative Examples were produced by the following method.
[0378] Embodiments 15 to 18
[0379] A mixture of inorganic fine particles, liquid dispersion medium A, liquid dispersion medium B, water, a pore former, and other components was stirred so as to have the component ratios listed in Table 1-4, and alkoxysilane was added and stirred to prepare an inorganic fine particle dispersion.
[0380] A substrate was prepared in which one side of the substrate was masked with a masking tape. Here, substrate-2 was used as the substrate.
[0381] For the above-mentioned substrate subjected to masking treatment, the prepared inorganic particle dispersion was applied to the side of the substrate that was not subjected to masking treatment using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, the masking tape was removed from the substrate and dried naturally at room temperature. For the obtained substrate, an oven was used to dry the substrate under the conditions of 100°C / 3 minutes in air, and then a muffle furnace was used to heat the substrate under the conditions of 700°C / 2 minutes in air, thereby forming an inorganic particle layer on the substrate, and a laminate comprising a substrate and an inorganic particle layer was obtained.
[0382] Comparative Example 10
[0383] Particle-5 (7.70 parts by mass), A-5 (21.40 parts by mass), 1 mol / L aqueous solution of Z-13 (0.50 parts by mass), and water (8.25 parts by mass) were stirred and mixed at 40°C, and C-3 (12.15 parts by mass) was further added while stirring, and stirred at 40°C for 8 hours. B-3 (22.07 parts by mass) was further added thereto and stirred to obtain a mixture. The mixture (28.58 parts by mass), B-3 (36.09 parts by mass), A-1 (2.40 parts by mass), and B-3 solution containing 10% by weight of P-2 (12.94 parts by mass) were stirred and mixed to obtain coating agent 10-1.
[0384] Separately, C-3 (13.88 parts by mass), B-3 solution (16.12 parts by mass), 1 mol / L aqueous solution of Z-13 (0.40 parts by mass), and water (9.60 parts by mass) were mixed and stirred at 40° C. for 8 hours to obtain a mixture. This mixture (15.24 parts by mass), B-3 (64.16 parts by mass), and an aqueous solution containing 10% by weight of Z-14 (0.60 parts by mass) were mixed and stirred to obtain a coating agent 10-2.
[0385] A substrate was prepared in which one side of the substrate was masked with a masking tape. Here, substrate-2 was used as the substrate.
[0386] For the substrate subjected to the masking treatment, the prepared coating agent 10-1 was applied to the non-masking surface of the substrate using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, the masking tape was removed from the substrate and naturally dried at room temperature. The obtained substrate was dried in an oven under the conditions of air / 100°C / 3 minutes, and then heated in a muffle furnace under the conditions of air / 350°C / 1 minute to obtain the substrate.
[0387] A substrate was prepared in which the non-coated surface of the obtained substrate was masked with a masking tape.
[0388] For the substrate obtained by masking the non-coated side, the prepared coating agent 10-2 was applied to the non-masked side of the substrate using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, the masking tape was removed from the substrate and dried naturally at room temperature. The obtained substrate was dried in an oven under air at 100°C for 3 minutes, and then heated in a muffle furnace under air at 700°C for 2 minutes, thereby obtaining a laminate comprising a substrate and an inorganic particle layer.
[0389] Comparative Example 11
[0390] The same coating agent as the above-mentioned coating agent 10-1 was prepared and this preparation was designated as coating agent 11-1.
[0391] Separately, C-3 (13.88 parts by mass), B-3 solution (16.12 parts by mass), 1 mol / L aqueous solution of Z-13 (0.40 parts by mass), and water (9.60 parts by mass) were mixed and stirred at 40° C. for 8 hours to obtain a mixture. This mixture (20.32 parts by mass), B-3 (55.88 parts by mass), and an aqueous solution containing 10% by weight of Z-14 (0.80 parts by mass) were mixed and stirred to obtain a coating agent 11-2.
[0392] A substrate was prepared in which one side of the substrate was masked with a masking tape. Here, substrate-2 was used as the substrate.
[0393] Using a slow dip coater MD-0408-01 (manufactured by SDI Co., Ltd.), the prepared coating agent 11-1 was applied to the non-masking side of the substrate subjected to the masking treatment. After coating, the masking tape was removed from the substrate and the substrate was naturally dried at room temperature. The obtained substrate was dried in an oven under air at 100°C for 3 minutes, and then heated in a muffle furnace under air at 350°C for 1 minute to obtain the substrate.
[0394] The obtained substrate was prepared by subjecting the non-coated surface side to masking treatment with a masking tape.
[0395] For the substrate with masking treatment on the non-coated side, the prepared coating agent 11-2 was applied to the non-masking side of the substrate using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, the masking tape was removed from the substrate and naturally dried at room temperature. The obtained substrate was dried in an oven under air / 100°C / 3 minutes, and then heated in a muffle furnace under air / 700°C / 2 minutes to obtain a laminate comprising a substrate and an inorganic particle layer.
[0396] Comparative Example 12
[0397] The inorganic fine particle dispersion was prepared by stirring a mixture of inorganic fine particles, liquid dispersion medium B, water, a pore former, and other components so as to have the component ratios shown in Table 1-5.
[0398] A substrate was prepared in which one side of the substrate was masked with a masking tape. Here, substrate-1 was used as the substrate.
[0399] For the above-mentioned substrate subjected to masking treatment, the prepared inorganic particle dispersion was applied to the side of the substrate that was not subjected to masking treatment using a micro-speed dip coater MD-0408-01 (manufactured by SDI Co., Ltd.). After coating, the masking tape was removed from the substrate and dried naturally at room temperature. For the obtained substrate, an oven was used to dry the substrate under the conditions of 100°C / 3 minutes in air, and then a muffle furnace was used to heat the substrate under the conditions of 700°C / 2 minutes in air, thereby forming an inorganic particle layer on the substrate, and a laminate comprising a substrate and an inorganic particle layer was obtained.
[0400] Evaluations of Examples and Comparative Examples were performed by the following methods.
[0401] The thickness of the smooth layer, the thickness of the porous layer, and the kurtosis of the brightness distribution in the scanning electron micrograph of the cross section were evaluated using an image of the cross section of the coating film observed using a scanning electron microscope (SEM) as described below.
[0402] Scanning electron microscope (SEM) observation
[0403] Scanning electron microscope (SEM) observation was performed according to the following operation steps. For sample preparation, a laminate comprising a glass substrate and an inorganic particle layer was cut to prepare a sample in which the cross section of the laminate was exposed. The obtained sample was fixed on a sample table using carbon tape in a manner such that the cross section was the upper part, and then carbon paste was applied to the side. For conductive treatment, Pt-Pd was evaporated to about 0.5 nm using an E1030 Ion Sputter manufactured by Hitachi High-Technologies Corporation.
[0404] The SEM was HITACHI SU8020 manufactured by Hitachi High-Technologies Corporation, and secondary electron images were formed using an acceleration voltage of 2 kV and an imaging mode of SE (U). The measurement magnification was set to 100,000 times, and 10 fields of view were measured.
[0405] [Thickness of smoothing layer]
[0406] The thickness of the smooth layer was evaluated using an image of a cross section of the coating film observed by the scanning electron microscope (SEM), and the thickness of the smooth layer was the average value of the thicknesses in three fields of view.
[0407] [Thickness of porous layer]
[0408] The thickness of the smooth layer was evaluated using an image of a cross section of the coating film observed by the scanning electron microscope (SEM), and the thickness of the porous layer was the average value of the thicknesses in 10 fields of view.
[0409] [Kurtosis of brightness distribution in scanning electron micrograph of cross section]
[0410] The kurtosis of the brightness distribution in the scanning electron microscope photograph of the cross section (sometimes also referred to as the kurtosis of the brightness distribution) was evaluated by the method shown below. For the gray scale image (10 fields of view) in the image of the coating cross section obtained by the above scanning electron microscope (SEM) observation, only the porous layer portion was adjusted in such a way that the image size became 50 pixels × 1280 pixels. For this adjusted portion, the kurtosis K of the brightness was calculated using the formula (X100) defined by Fisher.
[0411]
[0412] In formula (X100), h and w are the longitudinal and lateral dimensions of the adjusted image, i and j are the longitudinal and lateral coordinates of the image, respectively. ij is the brightness of the coordinate (i, j), μ and σ are the average value and standard deviation of the brightness, respectively, and are calculated by the following formulas (Y100) and (Z100).
[0413]
[0414]
[0415] The kurtosis K of the brightness in each field of view was calculated, and the average value in 10 fields of view was taken as the kurtosis of the brightness distribution in the scanning electron micrograph of the cross section.
[0416] [Surface roughness Sa]
[0417] The surface roughness Sa of the outer surface of the smooth layer was evaluated in the following manner using a scanning probe microscope (SPM).
[0418] SPM measurement conditions
[0419] Device: Made by Bruker, Dimension Icom
[0420] Cantilever: Made by Bruker, Part: MPP-11120 (Model: RTESPA)
[0421] T (thickness): 3.75 μm, L (length): 125 μm, W (width): 35 μm
[0422] f0 (resonance frequency): 300kHz, k (spring constant): 40N / m
[0423] Mode: Soft Tapping
[0424] Setting parameters
[0425]
[0426] Scanning probe microscopy (SPM) measurements were performed according to the following procedures.
[0427] A sample of a laminate including a glass substrate and an inorganic fine particle layer was fixed on a sample stage of the SPM so that the coating film was on the upper side. The fixing was performed by vacuum adsorption.
[0428] The SPM used Dimension Icom manufactured by Bruker, and the cantilever used MMP-11120 (RTESPA) manufactured by Bruker. The measurement was performed at a scan size of 1 μm×1 μm and a scan rate of 0.501 Hz. The obtained image was set to 256 pixels×256 pixels, and the feedback was measured by setting the integral gain to 1, the proportional gain to 5, and the amplitude set point to 300 mV.
[0429] The obtained height sensor image was flattened with Flatten Order: 1st, Number Histogram Bins: 512, Threshold Height: 0 nm, and the arithmetic mean height Sa of the contour surface was calculated based on the definition of ISO 25178-2: 2012, JIS B 0681-2: 2018. The average value of Sa under two fields of view was taken as the surface roughness Sa of the outer surface of the smooth layer.
[0430] [Spectral transmittance]
[0431] The total light transmittance of the laminated body was measured using an ultraviolet visible near infrared spectrophotometer UV-3150 (manufactured by Shimadzu Corporation), wherein the laminated body comprises a layer, wherein the layer comprises a substrate and inorganic particles. Then, the value of the total light transmittance in the region with a wavelength of 380 nm or more and 1100 nm or less was read from the obtained total light transmittance spectrum, and the average value was calculated.
[0432] The spectral transmittance of the obtained laminate was observed to increase relative to that of the uncoated substrate. The increase in spectral transmittance is defined as follows.
[0433] [Increase in spectral transmittance (%)]
[0434] =[spectral transmittance of the laminate (%)]-[spectral transmittance of the uncoated substrate (%)]
[0435] [Coating film adhesion]
[0436] The adhesiveness of the laminate was evaluated by a cross-cut cellophane tape peeling test. Cellophane tape used was LP-24 (manufactured by Michelbon Co., Ltd.). The peeling state after performing the test on 100 1 mm squares was observed and evaluated as follows.
[0437] ○: No peeling at all
[0438] △: The number of peeled pieces is less than 10
[0439] ×: The number of peeled pieces is greater than 10
[0440] [Antifouling properties]
[0441] In the above-mentioned checkered tape peeling test, laminates in which the inorganic fine particle layer did not peel significantly and in which the adhesive of the tape did not transfer to the coating surface after the tape was peeled were judged to have good antifouling properties and were evaluated as follows.
[0442] 0: No glue transfer
[0443] △: There is local transfer of glue
[0444] ×: Adhesive transfer occurs on the entire surface
[0445]
[0446]
[0447] exist Figure 1 A scanning electron microscope photograph of the cross section of Example 18 is shown in FIG.
[0448] exist Figure 2 A scanning electron microscope photograph of a cross section of Comparative Example 10 is shown in FIG.
[0449] exist Figure 3 A scanning electron microscope photograph of the cross section of Comparative Example 12 is shown in FIG.
[0450] It can be seen that Examples 15 to 18 have a small peak in brightness distribution, a large increase in spectral transmittance, and good coating adhesion and antifouling properties. On the other hand, Comparative Examples 10 to 11 have a large peak in brightness distribution and a small increase in spectral transmittance compared to Examples 15 to 18. In Comparative Example 12, no smooth layer was observed, and the surface roughness Sa was large compared to Examples 15 to 18, resulting in poor antifouling properties.
[0451] Industrial Applicability
[0452] According to the present invention, it is possible to provide an inorganic fine particle dispersion liquid capable of forming a layer having higher light transmittance and excellent antifouling properties.
[0453] According to the present invention, it is also possible to provide a laminate having a layer having a higher light transmittance and excellent antifouling properties.
[0454] In addition, the layer formed by the inorganic particle dispersion of the present invention has high hydrophilicity on the surface of the layer through the silanol group on the silicon dioxide contained in the layer, and also has the antifouling performance of washing away dirt with water and rain. These layers can be used as antireflection film, antifouling film, antifouling film, etc. As the example of specific use, the antireflection film and antifouling film of the surface of the protective glass of the solar cell (solar cell protective glass), the antireflection film for display, the antifouling film of agricultural film (plastic greenhouse), mirror, glass window, lighting, lens, antireflection film, antifouling film and antifouling film of sensor class, etc., are not limited to this. It is applicable to various films in the above-mentioned uses, various housing equipment machine parts headed by film, various agricultural parts, various industrial parts, various building materials parts, various parts of household appliances, various automotive interior parts and exterior parts, etc., in the construction industry, transportation machinery industry, in the fields of industries such as electrical and electronic industry and household goods, there is high practicality.
[0455] In addition, according to the second invention of the present invention, even on the substrate with light transmittance being substantially 0%, a laminate having a layer with excellent antifouling property and film adhesion can be provided. Through the silanol groups on the silicon dioxide contained in the layer, the hydrophilicity of the layer surface is high, and it also has the antifouling property of washing away dirt with water and rain. These layers can be used as antifouling films, and as examples of specific uses, various housing equipment machine parts, various agricultural parts, various industrial parts, various building material parts, various parts of household appliances, various automotive interior decoration parts and exterior decoration parts headed by outer walls, roofs, air conditioners, kitchens, bathrooms, washrooms, toilets, heat exchangers, exterior materials, logos, display components, etc. can be cited, and there are high practicality in the fields of industries such as building construction industry, transportation machinery industry, electrical and electronic industry, household goods, etc.
[0456] In addition, further according to the third invention of the present invention, it is possible to provide a laminated body with a coating structure having a higher light transmittance and excellent antifouling property. In addition, the laminated body of the present invention has a high hydrophilicity on the surface of the layer through the silanol group on the silicon dioxide contained in the layer, and also has the antifouling property of washing away dirt with water and rain. These layers can be used as antireflection films, antifouling films, antifouling films, antifogging films, etc. As examples of specific uses, the antireflection films and antifouling films on the surface of the protective glass of solar cells (solar cell protective glass), antireflection films for displays, antifogging films for agricultural films (plastic greenhouses), mirrors, glass windows, lighting, lenses, antireflection films, antifouling films and antifogging films of sensors, etc., are not limited thereto. It is applicable to various films in the above-mentioned uses, various housing equipment machine parts headed by films, various agricultural parts, various industrial parts, various building material parts, various parts of household appliances, various automotive interior and exterior parts, etc., in the construction industry, the transportation machinery industry, the electrical and electronic industry, the various fields of industries such as household goods, and has high practicality.
Claims
1. An inorganic particle dispersion, comprising: Inorganic particles, Liquid dispersion medium A with a boiling point greater than 121°C and less than 190°C, Liquid dispersion medium B with a boiling point less than 100°C, water, Alkoxysilane, and Pore formers, wherein When the total amount of the inorganic fine particle dispersion is 100 mass %, the content of the liquid dispersion medium A is 0.5 mass % or more and less than 15.0 mass %.
2. The inorganic fine particle dispersion according to claim 1, wherein The ratio of the weight of SiO2 contained in the alkoxysilane to the weight of the inorganic fine particles ([the weight of SiO2 contained in the alkoxysilane] / [the weight of the inorganic fine particles]) is greater than 0.
10.
3. The inorganic fine particle dispersion according to claim 1, wherein Alkoxysilane has a structure represented by the following general formula (1): General formula (1) (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms, and n is an integer of 2 to 1000).
4. The inorganic fine particle dispersion according to claim 1, wherein The inorganic fine particles are inorganic fine particles containing silicon dioxide particles.
5. The inorganic fine particle dispersion according to claim 1, wherein The pore former is an organic ammonium salt.
6. The inorganic fine particle dispersion according to claim 1, wherein The ratio of the weight of the pore former to the total weight of SiO 2 contained in the alkoxysilane ([weight of the pore former] / [total weight of SiO 2 contained in the alkoxysilane]) is 0.10 or more.
7. A method for producing a laminate, wherein: The method for manufacturing the laminate comprises: A step of coating the inorganic fine particle dispersion according to any one of claims 1 to 6 on a substrate (coating step); and A step of removing the liquid dispersion medium A, the liquid dispersion medium B and water from the inorganic fine particle dispersion applied on the substrate to form an inorganic fine particle layer on the substrate (dispersion medium removal step).
8. The method for producing a laminate according to claim 7, wherein: The method for producing a laminate further includes a heat treatment step after the dispersion medium removal step.
9. A laminated body, wherein: The laminate can be obtained by the method according to claim 7.
10. A laminated body, wherein: The laminate is obtained by coating an inorganic fine particle dispersion on a substrate having a light transmittance of substantially 0%, wherein the inorganic fine particle dispersion comprises: Inorganic particles, Liquid dispersion medium A with a boiling point greater than 121°C and less than 190°C, A liquid dispersion medium B having a boiling point of less than 100°C, and water, When the total amount of the inorganic fine particle dispersion is 100 mass %, the content of the liquid dispersion medium A is 0.5 mass % or more and less than 15 mass %.
11. The laminate according to claim 10, wherein: The inorganic fine particle dispersion further contains alkoxysilane.
12. The laminate according to claim 10, wherein The substrate having a light transmittance of substantially 0% is a metal substrate.
13. The laminate according to claim 11, wherein In the inorganic fine particle dispersion, the ratio of the weight of SiO2 contained in the alkoxysilane to the weight of the inorganic fine particles ([the weight of SiO2 contained in the alkoxysilane] / [the weight of the inorganic fine particles]) is greater than 0.
10.
14. The laminate according to claim 11, wherein Alkoxysilane has a structure represented by the following general formula (1): General formula (1) (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms, and n is an integer of 2 to 1000).
15. The laminate according to claim 10, wherein: The inorganic fine particles are inorganic fine particles containing silicon dioxide particles.
16. The laminate according to claim 11, wherein The inorganic fine particle dispersion contains a pore former.
17. The laminate according to claim 16, wherein The pore former is an organic ammonium salt.
18. The laminate according to claim 16, wherein In the inorganic fine particle dispersion, the ratio of the weight of the pore former to the total weight of SiO 2 contained in the alkoxysilane ([weight of the pore former] / [total weight of SiO 2 contained in the alkoxysilane]) is 0.10 or more.
19. The method for producing a laminate according to claim 10, wherein: The method for manufacturing the laminate comprises: a step of coating the inorganic fine particle dispersion on a substrate (coating step); and A step of removing the liquid dispersion medium A, the liquid dispersion medium B and water from the inorganic fine particle dispersion applied on the substrate to form an inorganic fine particle layer on the substrate (dispersion medium removal step).
20. The method for producing a laminate according to claim 19, wherein: The method for producing a laminate further includes a heat treatment step after the dispersion medium removal step.
21. A laminate comprising a substrate and a coating film applied on at least one of its main surfaces, wherein: The coating film comprises a smooth layer and a porous layer. The smooth layer exists on the outermost side of the coating film. The smoothing layer contains silicon dioxide, The smooth layer has a thickness of 5 nm to 50 nm, and the surface roughness Sa of the outer surface of the smooth layer is 4.70 nm or less. The porous layer is present between the smooth layer and the substrate, The porous layer contains silicon dioxide, The porous layer has a thickness of 60 nm to 200 nm. The kurtosis of the brightness distribution of the cross section of the porous layer in a scanning electron microscope photograph is 0.320 or less.
22. The laminate according to claim 21, wherein The laminate is obtained by coating an inorganic fine particle dispersion, wherein the inorganic fine particle dispersion comprises: Inorganic particles, Liquid dispersion medium A with a boiling point greater than 121°C and less than 190°C, Liquid dispersion medium B with a boiling point less than 100°C, water, Alkoxysilane, and Pore forming agent, When the total amount of the inorganic fine particle dispersion is 100 mass %, the content of the liquid dispersion medium A is 0.5 mass % or more and less than 15.0 mass %.
23. The laminate according to claim 22, wherein: The primary particle size of the inorganic fine particles is greater than or equal to 1 nm and less than 30 nm.
24. The laminate according to claim 22, wherein: In the inorganic fine particle dispersion, the ratio of the weight of SiO2 contained in the alkoxysilane to the weight of the inorganic fine particles ([the weight of SiO2 contained in the alkoxysilane] / [the weight of the inorganic fine particles]) is greater than 0.
10.
25. The laminate according to claim 22, wherein: Alkoxysilane has a structure represented by the following general formula (1): General formula (1) (In the formula, each R independently represents an alkyl group having 1 to 6 carbon atoms, and n is an integer of 2 to 1000).
26. The laminate according to claim 22, wherein: The inorganic fine particles are inorganic fine particles containing silicon dioxide particles.
27. The laminate according to claim 22, wherein The pore former is an organic ammonium salt.
28. The laminate according to claim 22, wherein: In the inorganic fine particle dispersion, the ratio of the weight of the pore former to the total weight of SiO 2 contained in the alkoxysilane ([weight of the pore former] / [total weight of SiO 2 contained in the alkoxysilane]) is 0.10 or more.
29. The laminate according to claim 21, wherein The laminate is manufactured by the following steps: a step of coating the inorganic fine particle dispersion on a substrate (coating step); and A step of removing the liquid dispersion medium A, the liquid dispersion medium B and water from the inorganic fine particle dispersion applied on the substrate to form an inorganic fine particle layer on the substrate (dispersion medium removal step).
30. The laminate according to claim 29, wherein The laminate is produced by a production method including a heat treatment step after the dispersion medium removal step.
31. The laminate according to claim 29, wherein The coating step was performed once.
Citation Information
Patent Citations
Production process of reflection preventive laminate
JP2006327187A
Paint composition for forming hardcoat layer, and optical component
WO2019044838A1
Coating liquid, cured film, multilayer body provided with said cured film, lighting component provided with said multilayer body, display, lens, component for solar cells, antireflective film, lighting cover, and lighting device
WO2020241745A1